Electrostatic charge image developing toner, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method

By optimizing the ratio and configuration of amorphous polyester resin, crystalline polyester resin and internally added cross-linked resin particles in the toner for electrostatic image development, the problems of insufficient low-temperature fixability and uneven transfer are solved, achieving efficient image transfer effect.

CN120722683APending Publication Date: 2025-09-30FUJIFILM BUSINESS INNOVATION CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510140943.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-10-03
Filing Date
2025-02-08
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

Conventional electrostatic image developing toners containing an amorphous polyester resin, a crystalline polyester resin, and internally added crosslinked resin particles have problems such as insufficient low-temperature fixability and a tendency to cause transfer unevenness.

Method used

By adopting a specific ratio of amorphous polyester resin and crystalline polyester resin and a storage modulus range of added cross-linked resin particles, the configuration of resin particles is controlled through emulsification coagulation method, the growth of crystalline polyester resin domains is suppressed, and the charge injection and transfer uniformity are improved.

Benefits of technology

Low-temperature fixing performance is achieved while transfer unevenness is suppressed, and the charge injection performance and transfer uniformity of the toner are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120722683A_ABST
    Figure CN120722683A_ABST
Patent Text Reader

Abstract

An electrostatic charge image developing toner, an electrostatic charge image developer, a toner cartridge, a process cartridge, an image forming apparatus, and an image forming method, the electrostatic charge image developing toner having toner particles containing an amorphous polyester resin and a crystalline polyester resin as binder resins and having crosslinked resin particles added therein, the toner particles contain an amorphous polyester resin (S) as the amorphous polyester resin, the amorphous polyester resin (S) having at least one of an alkyl group having 8-15 carbon atoms and an alkenyl group having 8-15 carbon atoms, the content of the crystalline polyester resin is from 10% by mass to 40% by mass (inclusive), and the internal crosslinked resin particles are styrene-(meth) acrylic copolymer particles having a storage modulus G'in the range of from 60 DEG C to 100 DEG C (inclusive) of from 1.0 * 105 Pa to 1.0 * 106 Pa (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a toner for developing an electrostatic image, an electrostatic image developer, a toner cartridge, a process cartridge, an image forming apparatus, and an image forming method. Background Art

[0002] Patent Document 1 discloses "a toner for developing electrostatic images, comprising toner particles, the toner particles containing a binder resin comprising a polyester resin, a release agent comprising a hydrocarbon wax, and a styrene (meth) acrylic resin, wherein 70% or more of the release agent is present within 800 nm from the surface of the toner particles, and in the toner particles, the styrene (meth) acrylic resin forms domains having an average diameter of less than 0.3 μm."

[0003] Patent Document 2 discloses a toner for electrostatic image development, comprising toner particles containing a binder resin, wherein, in a dynamic viscoelasticity measurement of the toner for electrostatic image development, a loss tangent tanδ at a temperature of 90°C and a strain of 1% is set as D1(90), a loss tangent tanδ at a temperature of 90°C and a strain of 50% is set as D50(90), a loss tangent tanδ at a temperature of 150°C and a strain of 1% is set as D1(150), and a loss tangent tanδ at a temperature of 150°C and a strain of 1% is set as D2(150). When the loss tangent tanδ at 50% of the toner volume is set to D50(150), D1(90), D50(90), D1(150) and D50(150) are respectively 0.5 or more and 2.5 or less, the value of D50(150)-D1(150) is less than 1.5, and the value of D50(90)-D1(90) is less than 1.0, the toner particles further contain resin particles, and the number average molecular weight of the tetrahydrofuran-soluble component in the toner particles is 5000 or more and 15000 or less.

[0004] Patent document 3 discloses "a toner for electrostatic image development, comprising toner particles containing a binder resin having a domain / matrix structure and a colorant, wherein the toner particles are particles having a volume-based median diameter of 4.3 to 7.0 μm, the matrix phase in the binder resin is composed of a polymer of a styrene-acrylic resin or a polyester resin, and the domain phase in the binder resin is composed of a polymer containing structural units derived from a diene monomer, the size of the domain phase is 50 to 300 nm in Feret diameter, and the glass transition temperature of the polymer constituting the domain phase is in the range of -85 to +35°C."

[0005] Patent Document 4 discloses “an electrophotographic toner using a crystalline polyester for toner, the crystalline polyester for toner being obtained by polycondensing an alcohol component containing an aliphatic diol having 2 to 8 carbon atoms with a carboxylic acid component containing at least one selected from an aromatic dicarboxylic acid and an alkyl succinic acid and an alkenyl succinic acid.”

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2016-62042

[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 2011-257744

[0008] Patent Document 3: Japanese Patent Application Laid-Open No. 2023-48127

[0009] Patent Document 4: Japanese Patent Application Laid-Open No. 2010-072215 Summary of the Invention

[0010] The present invention aims to provide a toner for developing electrostatic images, wherein the toner comprises toner particles containing an amorphous polyester resin and a crystalline polyester resin as a binder resin, and internally added crosslinked resin particles, wherein the content of the crystalline polyester resin relative to the binder resin is 10% by mass or more and 40% by mass or less, and the amorphous polyester resin is exclusively an amorphous polyester resin without at least one of an alkyl group having 8 or more and 15 or less carbon atoms and an alkenyl group having 8 or more and 15 or less carbon atoms, and the internally added crosslinked resin particles have a storage modulus G' of less than 1.0×10-1 within a range of 60° C. or more and 100° C. or less. 5 Pa or more than 1.0×10 6 In the case of the styrene-(meth)acrylic acid-based copolymer particles of Pa, low-temperature fixing properties are achieved, and transfer unevenness can be suppressed.

[0011] Means for solving the above-mentioned problems include the following.

[0012] <1>

[0013] A toner for developing electrostatic images, comprising toner particles containing an amorphous polyester resin and a crystalline polyester resin as binder resins and internally added crosslinked resin particles.

[0014] The toner particles contain an amorphous polyester resin (S) as the amorphous polyester resin, wherein the amorphous polyester resin (S) has at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms.

[0015] The content of the crystalline polyester resin is 10% by mass or more and 40% by mass or less relative to the binder resin,

[0016] The storage modulus G' of the internally added cross-linked resin particles in the range of 60°C to 100°C is 1.0×10 5 Pa or more and 1.0×10 6 Pa or less styrene-(meth)acrylic acid copolymer particles.

[0017] <2>

[0018] The electrostatic image developing toner according to <1>, wherein

[0019] A ratio Wb / Wa of a content Wa of the amorphous polyester resin to a content Wb of the internally added crosslinked resin particles relative to the toner particles is 0.05 or more and 0.50 or less in terms of mass ratio.

[0020] <3>

[0021] The electrostatic image developing toner according to <2>, wherein

[0022] A ratio Wb / Wa of a content Wa of the amorphous polyester resin to a content Wb of the internally added crosslinked resin particles relative to the toner particles is 0.10 or more and 0.35 or less in terms of mass ratio.

[0023] <4>

[0024] The electrostatic image developing toner according to any one of <1> to <3>, wherein

[0025] A ratio Wb / Wc of a content Wc of the crystalline polyester resin to a content Wb of the internally added crosslinked resin particles relative to the toner particles is 0.20 or more and 2.00 or less in terms of mass ratio.

[0026] <5>

[0027] The electrostatic image developing toner according to <4>, wherein

[0028] A ratio Wb / Wc of a content Wc of the crystalline polyester resin to a content Wb of the internally added crosslinked resin particles relative to the toner particles is 0.50 or more and 1.00 or less in terms of mass ratio.

[0029] <6>

[0030] The electrostatic image developing toner according to any one of <1> to <5>, wherein

[0031] The amorphous polyester resin (S) is an amorphous polyester resin having a structural unit PC derived from a polycarboxylic acid and a structural unit PA derived from a polyol.

[0032] At least a portion of the structural units PC and PA are structural units having at least one of the alkyl group and the alkenyl group.

[0033] The ratio of the structural unit having at least one of the alkyl group and the alkenyl group is 2 mol% or more and 25 mol% or less in terms of a molar ratio relative to all structural units constituting the amorphous polyester resin.

[0034] <7>

[0035] The electrostatic image developing toner according to <6>, wherein

[0036] The ratio of the structural unit having at least one of the alkyl group and the alkenyl group is 5 mol% or more and 20 mol% or less in terms of a molar ratio relative to all structural units constituting the amorphous polyester resin.

[0037] <8>

[0038] The electrostatic image developing toner according to <6> or <7>, wherein

[0039] At least one of the alkyl group and the alkenyl group is present only in at least a portion of the structural units PC derived from the polycarboxylic acid.

[0040] <9>

[0041] The electrostatic image developing toner according to any one of <1> to <8>, wherein

[0042] The average dispersion diameter of the internally added cross-linked resin particles is 100 nm or more and 300 nm or less.

[0043] <10>

[0044] The electrostatic image developing toner according to any one of <1> to <9>, wherein

[0045] The dielectric loss coefficient of the toner at 1 kHz after being left at a temperature of 28° C. and a relative humidity of 85% RH is 35×10 -3 the following.

[0046] <11>

[0047] The electrostatic image developing toner according to any one of <1> to <10>, wherein

[0048] The toner particles contain carbon black as a colorant.

[0049] <12>

[0050] An electrostatic image developer comprising the electrostatic image developing toner according to any one of <1> to <11>.

[0051] <13>

[0052] A toner cartridge containing the electrostatic image developing toner described in any one of <1> to <11>,

[0053] The image forming apparatus is mounted and removed from the image forming apparatus.

[0054] <14>

[0055] A process cartridge comprising a developing device that contains the electrostatic image developer described in <12> and develops an electrostatic image formed on a surface of an image holding member into a toner image using the electrostatic image developer.

[0056] The process cartridge is attachable to and detachable from the image forming apparatus.

[0057] <15>

[0058] An image forming apparatus comprising:

[0059] Image holding body;

[0060] a charging device for charging the surface of the image holding member;

[0061] an electrostatic image forming device for forming an electrostatic image on the charged surface of the image holding member;

[0062] a developing device that accommodates the electrostatic image developer described in <12> and develops the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer;

[0063] a transfer device that transfers the toner image formed on the surface of the image holding member to the surface of a recording medium; and

[0064] The fixing device fixes the toner image transferred onto the surface of the recording medium.

[0065] <16>

[0066] An image forming method comprising:

[0067] a charging process for charging the surface of the image holding member;

[0068] an electrostatic image forming step of forming an electrostatic image on the charged surface of the image holding member;

[0069] a developing step of developing the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer described in <12>;

[0070] a transfer step of transferring the toner image formed on the surface of the image holding member to the surface of a recording medium; and

[0071] The fixing step fixes the toner image transferred onto the surface of the recording medium.

[0072] Effects of the Invention

[0073] According to the invention <1>, there is provided a toner for developing electrostatic images: compared to a case where, in a toner having toner particles comprising an amorphous polyester resin and a crystalline polyester resin as a binder resin, and internally added crosslinked resin particles, the content of the crystalline polyester resin relative to the binder resin is 10% by mass or more and 40% by mass or less, the amorphous polyester resin is solely an amorphous polyester resin having no at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms, and the internally added crosslinked resin particles have a storage elastic modulus G' of less than 1.0×10 5 Pa or more than 1.0×10 6 In the case of the styrene-(meth)acrylic acid-based copolymer particles of Pa, low-temperature fixing properties are achieved, and transfer unevenness can be suppressed.

[0074] According to the invention <2>, there is provided a toner for developing electrostatic images having low-temperature fixing properties and capable of suppressing transfer unevenness, compared to a case where the ratio Wb / Wa of the content Wa of the amorphous polyester resin to the content Wb of the internally added cross-linked resin particles relative to the toner particles is less than 0.05 or exceeds 0.50 in terms of mass ratio.

[0075] According to the invention <3>, there is provided a toner for developing electrostatic images having low-temperature fixing properties and capable of suppressing transfer unevenness, compared to a case where the ratio Wb / Wa of the content Wa of the amorphous polyester resin to the content Wb of the internally added crosslinked resin particles relative to the toner particles is less than 0.10 or exceeds 0.35 in terms of mass ratio.

[0076] According to the invention according to <4>, there is provided a toner for developing electrostatic images having low-temperature fixing properties and capable of suppressing transfer unevenness, compared to a case where the ratio Wb / Wc of the content Wc of the crystalline polyester resin to the content Wb of the internally added crosslinked resin particles relative to the toner particles is less than 0.20 or exceeds 2.00 in terms of mass ratio.

[0077] According to the invention according to <5>, there is provided a toner for developing electrostatic images having low-temperature fixing properties and capable of suppressing transfer unevenness, compared to a case where the ratio Wb / Wc of the content Wc of the crystalline polyester resin to the content Wb of the internally added crosslinked resin particles relative to the toner particles is less than 0.50 or exceeds 1.00 in terms of mass ratio.

[0078] According to the invention according to <6>, there is provided a toner for developing electrostatic images, which has low-temperature fixing properties and can suppress transfer unevenness, compared to a case where the proportion of structural units having at least one of an alkyl group and an alkenyl group is less than 2 mol % or exceeds 25 mol % in terms of the molar ratio relative to all structural units constituting the amorphous polyester resin.

[0079] According to the invention according to <7>, there is provided a toner for developing electrostatic images, which has low-temperature fixing properties and can suppress transfer unevenness, compared to a case where the proportion of structural units having at least one of an alkyl group and an alkenyl group is less than 5 mol % or exceeds 20 mol % in terms of the molar ratio relative to all structural units constituting the amorphous polyester resin.

[0080] According to the invention <8>, there is provided a toner for developing electrostatic images that is low-cost, has low-temperature fixing properties, and can suppress transfer unevenness, compared to a case where at least one of an alkyl group and an alkenyl group is contained in at least a portion of the structural units PA derived from a polyol.

[0081] According to the invention <9>, there is provided a toner for developing electrostatic images having low-temperature fixing properties and capable of suppressing transfer unevenness compared to a toner containing internally added crosslinked resin particles having an average dispersion diameter of less than 100 nm or exceeding 300 nm.

[0082] According to the invention according to <10>, there is provided a toner for developing an electrostatic image having a dielectric loss coefficient of more than 35×10 -3 In the case of , it has low-temperature fixing properties and can suppress transfer unevenness.

[0083] According to the invention according to <11>, there is provided a toner for developing electrostatic images: compared to a case where, in a toner comprising toner particles containing an amorphous polyester resin and a crystalline polyester resin as a binder resin and internally added crosslinked resin particles, the content of the crystalline polyester resin relative to the toner particles is 10% by mass or more and 40% by mass or less, the amorphous polyester resin is an amorphous polyester resin having no at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms, and the internally added crosslinked resin particles have a storage modulus G' of less than 1.0×10 5 Pa or more than 1.0×10 6 In the case of the styrene-(meth)acrylic acid copolymer particles of Pa, even if the toner particles contain carbon black as a colorant, low-temperature fixing properties are achieved and transfer unevenness can be suppressed.

[0084] According to the invention of <12>, <13>, <14>, <15>, or <16>, there is provided an electrostatic image developer, a toner cartridge, a process cartridge, an image forming apparatus, or an image forming method: compared to a case where, in a toner for electrostatic image development comprising toner particles containing an amorphous polyester resin and a crystalline polyester resin as a binder resin and internally added crosslinked resin particles, the content of the crystalline polyester resin relative to the toner particles is 10% by mass or more and 40% by mass or less, the amorphous polyester resin is an amorphous polyester resin that does not have at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms, and the internally added crosslinked resin particles have a storage modulus G' of less than 1.0×10 5 Pa or more than 1.0×10 6 In the case of the styrene-(meth)acrylic acid-based copolymer particles of Pa, low-temperature fixing properties are achieved, and transfer unevenness can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0085] Embodiments of the present invention will be described in detail with reference to the following drawings.

[0086] Figure 1 FIG. 1 is a schematic structural diagram showing an example of an image forming apparatus according to the present embodiment;

[0087] Figure 2 This is a schematic structural diagram showing an example of a process cartridge that is attached to and detached from the image forming apparatus according to the present embodiment.

[0088] Explanation of symbols

[0089] 1Y, 1M, 1C, 1K - photoreceptor (an example of an image holding member), 2Y, 2M, 2C, 2K - charging roller (an example of a charging device), 3 - exposure device (an example of an electrostatic image forming device), 3Y, 3M, 3C, 3K - laser beam, 4Y, 4M, 4C, 4K - developing device (an example of a developing device), 5Y, 5M, 5C, 5K - primary transfer roller (an example of a primary transfer device), 6Y, 6M, 6C, 6K - photoreceptor cleaning device (an example of a cleaning device), 8Y, 8M, 8C, 8K - toner cartridge, 10Y, 10M, 10C, 10K - image forming unit, 20 - intermediate transfer belt (an example of an intermediate transfer member), 22 - drive roller, 24 - backup roller, 26 - Secondary transfer roller (an example of a secondary transfer device), 28-fixing device (an example of a fixing device), 30-intermediate transfer body cleaning device, 107-photoreceptor (an example of an image holding body), 108-charging roller (an example of a charging device), 109-exposure device (an example of an electrostatic image forming device), 111-developing device (an example of a developing device), 112-transfer device (an example of a transfer device), 113-photoreceptor cleaning device (an example of a cleaning device), 115-fixing device (an example of a fixing device), 116-mounting guide, 118-opening portion for exposure, 117-housing, 200-processing box, 300-recording paper (an example of a recording medium), P-recording paper (an example of a recording medium). DETAILED DESCRIPTION

[0090] Hereinafter, an embodiment of the present invention will be described. These descriptions and examples illustrate the embodiment and do not limit the scope of the invention.

[0091] In the numerical ranges described in stages in this specification, the upper limit or lower limit described in one numerical range may be replaced by the upper limit or lower limit of another numerical range described in stages. Furthermore, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may also be replaced by the value shown in the Examples.

[0092] In this specification, (meth)acrylic acid refers to both acrylic acid and methacrylic acid.

[0093] In this specification, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.

[0094] Each component may contain multiple corresponding substances.

[0095] When referring to the amount of each component in a composition, if there are multiple substances corresponding to each component in the composition, unless otherwise specified, the amount refers to the total amount of the multiple substances present in the composition.

[0096] [Toner for electrostatic image development]

[0097] The electrostatic image developing toner (hereinafter also referred to as “toner”) according to the present embodiment includes toner particles containing an amorphous resin and a crystalline resin as binder resins, and internally added crosslinked resin particles.

[0098] The toner particles contain, as the amorphous polyester resin, an amorphous polyester resin (S) having at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms.

[0099] The content of the crystalline polyester resin is 10% by mass or more and 40% by mass or less relative to the binder resin.

[0100] Furthermore, the storage modulus G' of the internally added cross-linked resin particles in the range of 60°C to 100°C is 1.0×10 5 Pa or more and 1.0×10 6 Pa or less styrene-(meth)acrylic acid copolymer particles.

[0101] The above-described structure enables the toner according to this embodiment to have low-temperature fixing properties and suppress transfer unevenness. The reason for this is presumably as follows.

[0102] Conventionally, toners using a combination of amorphous and crystalline polyester resins to achieve both low-temperature fixing and heat storage properties are known. However, because crystalline polyester resins have lower electrical resistivity than amorphous polyester resins, when the crystalline polyester resin content relative to the binder resin is increased to 10% to 40% by mass, crystalline polyester resin domains grow within the toner particles, easily forming conductive paths within the toner. This results in reduced transferability, which manifests as transfer unevenness in the resulting image.

[0103] In order to improve the reduction in transferability, for example, inside the toner particles, the domains of the crystalline polyester resin are preferably kept small.

[0104] However, for example, technologies for incorporating internally added crosslinked resin particles within toner particles are known (Patent Documents 1 and 3, etc.). The presence of internally added crosslinked resin particles may inhibit the domain growth of a portion of the crystalline polyester resin. However, during the production of toner particles, the arrangement of the internally added crosslinked resin particles and the crystalline polyester resin cannot be controlled, making it difficult to inhibit the domain growth of the crystalline polyester resin.

[0105] To properly arrange the internally added crosslinked resin particles and the crystalline polyester resin within the toner particles, it is particularly preferred to produce the toner particles using, for example, an emulsion coagulation method. In this emulsion coagulation method, amorphous polyester resin particles, crystalline polyester resin particles, and internally added crosslinked resin particles are dispersed in water and gradually coagulate, thereby gradually forming the structure of the toner particles. During this toner particle formation process, for example, the internally added crosslinked resin particles and the crystalline polyester resin particles preferably coagulate in close proximity, and this state is maintained until the toner particle fusion step is completed.

[0106] In conventional toners, temperatures slightly above room temperature are above the glass transition temperature of the internally added cross-linked resin particles, but below the glass transition temperature of the amorphous polyester resin. In this case, the internally added cross-linked resin particles have strong adhesion, resulting in the formation of aggregates from the monomers. Consequently, at temperatures around the melting point of the crystalline polyester resin, crystalline polyester resin domains grow in areas of the internally added cross-linked resin particles other than the aggregates. This results in a structure where the crystalline polyester resin easily forms conductive paths, impairing the charge injection properties of the toner particles. Consequently, transfer unevenness occurs.

[0107] In contrast, the toner according to this embodiment employs an amorphous polyester resin (S) having at least one of an alkyl group with 8 to 15 carbon atoms and an alkenyl group with 8 to 15 carbon atoms. When the amorphous polyester resin employs a resin having at least one of the highly mobile alkyl or alkenyl groups, the movement of the alkyl or alkenyl groups in the amorphous polyester resin and the surface movement of the amorphous polyester resin particles enhance the physical adhesion of the amorphous polyester resin particles. This suppresses the formation of aggregates by the internally added cross-linked resin particles. Specifically, the internally added cross-linked resin particles are trapped by the amorphous polyester, making agglomeration difficult. The crystalline polyester resin is then positioned in the gaps between the particles, thereby suppressing the formation of conductive paths by the crystalline polyester resin.

[0108] Furthermore, the internally added cross-linked resin particles having the aforementioned storage elastic modulus G' exhibit elastic properties at high temperatures ranging from 60°C to 100°C. Therefore, during aggregation, the internally added cross-linked resin particles can exist in a nearly uniform state within the toner particles without fusing or forming domains, thereby suppressing the migration of the crystalline polyester resin and the growth of domains.

[0109] As a result, deterioration in the charge injection property of the toner particles is suppressed, and the occurrence of transfer unevenness is suppressed.

[0110] Based on the above, it is presumed that the toner according to this embodiment has low-temperature fixing properties and can suppress transfer unevenness.

[0111] Hereinafter, the toner according to this embodiment will be described in detail.

[0112] The toner according to this embodiment includes toner particles. The toner according to this embodiment may include external additives.

[0113] (Toner particles)

[0114] The toner particles contain amorphous resin and crystalline resin as binder resins and internally added crosslinked resin particles. The toner particles may also contain a colorant, a release agent, and other additives.

[0115] -Binding resin-

[0116] As the binder resin, amorphous polyester resin and crystalline polyester resin are suitable.

[0117] However, from the viewpoint of ensuring low-temperature fixing properties and suppressing transfer unevenness, the content of the crystalline polyester resin relative to the binder resin is 10% by mass or more and 40% by mass or less, for example, preferably 10% by mass or more and 30% by mass or less, and more preferably 15% by mass or more and 20% by mass or less.

[0118] If the content of the crystalline polyester resin is less than 10% by mass, low-temperature fixing property decreases.

[0119] If the content of the crystalline polyester resin exceeds 40% by mass, domain growth of the crystalline polyester resin cannot be suppressed, resulting in transfer unevenness.

[0120] The "crystallinity" of a resin refers to the presence of a clear endothermic peak in differential scanning calorimetry (DSC) rather than a step-like change in endothermic value. Specifically, it refers to the half-width of the endothermic peak being within 10°C when measured at a heating rate of 10°C / min.

[0121] On the other hand, the "amorphous nature" of a resin means that the half-value width exceeds 10° C., a step-like change in endothermic value is observed, or a clear endothermic peak cannot be confirmed.

[0122] The amorphous polyester resin will be described.

[0123] The amorphous polyester resin contains an amorphous polyester resin (S) having at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms.

[0124] Specifically, the amorphous polyester resin is a condensation product of a polycarboxylic acid and a polyol, that is, an amorphous polyester resin having structural units PC derived from a polycarboxylic acid and structural units PA derived from a polyol, and the amorphous polyester resin (S) contains structural units in which at least a portion of the structural units PC and the structural units PA are structural units having at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms.

[0125] If the number of carbon atoms of the alkyl group and the alkenyl group is less than 8, the molecular motion of the resin based on the alkyl group and the alkenyl group is reduced, and the domain growth of the crystalline polyester resin cannot be suppressed, resulting in transfer unevenness.

[0126] If the number of carbon atoms in the alkyl and alkenyl groups exceeds 15, excessive molecular motion of the resins based on the alkyl and alkenyl groups occurs, making it easier for amorphous polyester resin particles to aggregate during toner particle formation. Consequently, domain growth of the crystalline polyester resin cannot be suppressed, leading to transfer unevenness.

[0127] From the viewpoint of suppressing transfer unevenness, the number of carbon atoms in the alkyl group and the alkenyl group is preferably, for example, 10 or more and 14 or less.

[0128] In addition, the number of carbon atoms of the alkyl or alkenyl group in the structural unit PC derived from the polycarboxylic acid is the number of carbon atoms excluding the carbon atoms of the carboxyl residue, and does not include the number of carbon atoms that form the main chain of the polycarboxylic acid during polymerization (i.e., the number of carbon atoms of the linear carbon chain formed by connecting two carboxyl groups in series). Specifically, if the polycarboxylic acid is C4H3O3-C 12 H 23 , then the number of carbon atoms is 12.

[0129] For example, it is preferred that the structural unit contain at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms in the side chain. By having at least one of a highly mobile alkyl group and an alkenyl group in the side chain of the amorphous polyester resin, it is possible to suppress an excessive decrease in the glass transition temperature of the amorphous polyester resin, thereby maintaining the powder properties of the toner particles and suppressing domain growth of the crystalline polyester resin. As a result, transfer unevenness is easily suppressed.

[0130] From the viewpoint of suppressing transfer unevenness, the proportion of structural units having at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms, relative to the molar ratio of all structural units constituting the amorphous polyester resin (i.e., all amorphous polyester resins contained in the toner particles), is, for example, preferably from 2 mol % to 25 mol %, and more preferably from 5 mol % to 20 mol %.

[0131] For example, the amorphous polyester resin in the toner particles is preferably entirely composed of an amorphous polyester resin (S) having at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms. Alternatively, the toner particles may contain an amorphous polyester resin other than the amorphous polyester resin (S) such that the proportion of structural units having at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms, relative to all structural units constituting the amorphous polyester resin in the toner particles (i.e., all amorphous polyester resins contained in the toner particles), is from 2 mol% to 25 mol%.

[0132] The ratio of the structural unit having at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms is measured as follows.

[0133] The toner is dissolved in a solvent such as tetrahydrofuran (THF) in which the binder resin is soluble to remove insoluble components, and then dried. Furthermore, the amorphous polyester resin and the crystalline polyester resin contained in the binder resin are separated using a solvent in which the amorphous polyester resin is soluble and the crystalline polyester resin is insoluble, utilizing the difference in solubility between the amorphous polyester resin and the crystalline polyester resin in the solvent. After confirming the absence of an endothermic peak derived from the crystalline polyester resin in the obtained amorphous polyester resin using a DSC (differential scanning calorimeter), the amorphous polyester resin is subjected to a separation process. 1 H-NMR measurement: The obtained NMR spectrum was analyzed to determine the chemical shift and the integral value ratio.

[0134] Then, the proportion (molar ratio) of structural units having at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms can be determined based on the chemical shift and the integrated value ratio.

[0135] From the viewpoint of easy availability and cost reduction, the amorphous polyester resin (S) is preferably a resin having at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms in the structural unit PC derived from a polycarboxylic acid.

[0136] From the viewpoint of suppressing transfer unevenness, the structural units PA derived from polycarboxylic acids and the structural units PC derived from polyols, other than the structural units having at least one of an alkyl group having 8 or more and 15 carbon atoms and an alkenyl group having 8 or more and 15 carbon atoms, are preferably structural units PA derived from aromatic polycarboxylic acids and structural units PC derived from aromatic polyols, respectively.

[0137] Therefore, specifically, for example, the amorphous polyester resin (S) preferably contains structural units derived from an aliphatic polycarboxylic acid having at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms, and an aromatic polycarboxylic acid, and structural units derived from an aromatic polyol. The amorphous polyester resin (S) particularly preferably contains structural units derived from an aliphatic polycarboxylic acid having at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms, and terephthalic acid, and structural units derived from an aromatic polyol.

[0138] Examples of the aliphatic polycarboxylic acid having at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms include octenylsuccinic acid, nonenylsuccinic acid, decenylsuccinic acid, undecenylsuccinic acid, dodecenylsuccinic acid, tridecenylsuccinic acid, tetradecenylsuccinic acid, pentadecenylsuccinic acid, and the like, and anhydrides thereof or lower (for example, having 1 to 5 carbon atoms) alkyl esters thereof.

[0139] Examples of the aromatic polycarboxylic acid include terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, and the like, and anhydrides or lower (for example, having 1 to 5 carbon atoms) alkyl esters thereof.

[0140] Regarding polycarboxylic acids, trivalent or higher carboxylic acids having a cross-linked structure or a branched structure may be used in combination with dicarboxylic acids. Examples of trivalent or higher carboxylic acids include trimellitic acid, pyromellitic acid, anhydrides thereof, or lower (e.g., carbon number 1 to 5) alkyl esters thereof.

[0141] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0142] Examples of the aliphatic polyol having at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms include 1,8-octanediol, 1,12-dodecanediol, 1,15-pentadecanediol, and 1-dodecenyl-1-ethanediol.

[0143] Examples of the aromatic polyol include ethylene oxide adducts of bisphenol A and propylene oxide adducts of bisphenol A.

[0144] As the polyol, a trivalent or higher polyol having a cross-linked structure or a branched structure may be used in combination with a diol. Examples of the trivalent or higher polyol include glycerin, trimethylolpropane, and pentaerythritol.

[0145] The polyols may be used alone or in combination of two or more.

[0146] The glass transition temperature (Tg) of the amorphous polyester resin is, for example, preferably 50° C. or higher and 80° C. or lower, and more preferably 50° C. or higher and 65° C. or lower.

[0147] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, according to the "extrapolated glass transition onset temperature" method described in JIS K 7121-1987 "Plastics - Determination of Transition Temperatures".

[0148] The weight average molecular weight (Mw) of the amorphous polyester resin is, for example, preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less.

[0149] The number average molecular weight (Mn) of the amorphous polyester resin is preferably, for example, 2,000 or more and 100,000 or less.

[0150] The molecular weight distribution Mw / Mn of the amorphous polyester resin is, for example, preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less.

[0151] The weight-average molecular weight and number-average molecular weight were measured by gel permeation chromatography (GPC). GPC-based molecular weight determinations were performed using a TOSOH Corporation GPC HLC-8120GPC as a measuring apparatus and a TOSOH Corporation column TSKgel SuperHM-M (15 cm) in a THF solvent. The weight-average molecular weight and number-average molecular weight were calculated using a molecular weight calibration curve prepared from the measurement results using monodisperse polystyrene standard samples.

[0152] The amorphous polyester resin is obtained by a known production method. Specifically, for example, the polymerization temperature is set to 180° C. to 230° C., and the pressure in the reaction system is reduced as needed to allow the reaction to proceed while removing water or alcohol generated during condensation.

[0153] Furthermore, if the raw monomers are insoluble or incompatible under the reaction temperature conditions, a high-boiling-point solvent may be added as a cosolvent to dissolve them. In this case, the polycondensation reaction proceeds while the cosolvent is distilled off. If a poorly miscible monomer is present, for example, the poorly miscible monomer can be pre-condensed with an acid or alcohol intended to be polycondensed with the monomer, and then polycondensed with the main component.

[0154] Here, the amorphous polyester resin may be used alone or in combination of two or more.

[0155] For example, the amorphous polyester resin preferably uses two or more amorphous polyesters having different molecular weights in combination. Examples of the combination of two amorphous polyester resins include a low molecular weight (L-isomer) amorphous polyester resin and a high molecular weight (H-isomer) amorphous polyester resin.

[0156] The low molecular weight form (L-form) is preferably an amorphous polyester resin having a weight average molecular weight of 9000 to 20000 as measured by GPC. If the molecular weight is less than 9000, the high temperature portion tends to shift, while if the molecular weight is 20000 or more, the low temperature portion tends to be less glossy.

[0157] The high molecular weight body (H body) is preferably an amorphous polyester resin having a polymerization average molecular weight of 25000 to 70000 as measured by GPC. A molecular weight of 70000 or more reduces glossiness in high temperature areas and reduces the increase in fixing temperature.

[0158] The acid value of the amorphous polyester resin used in combination is preferably, for example, about 13 mgKOH / g to 20 mgKOH / g for the low molecular weight form (L form) and about 10 mgKOH / g to 15 mgKOH / g for the high molecular weight form (H form).

[0159] The crystalline polyester resin will be described.

[0160] Examples of the crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. A commercially available crystalline polyester resin may be used, or a synthetic resin may be used.

[0161] Here, in order to easily form a crystal structure, the crystalline polyester resin is preferably a polycondensate of a polymerizable monomer having a linear aliphatic group, rather than a polycondensate of a polymerizable monomer having an aromatic group.

[0162] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalene-2,6-dicarboxylic acid), anhydrides thereof, or lower (e.g., having 1 to 5 carbon atoms) alkyl esters thereof.

[0163] Regarding polycarboxylic acids, trivalent or higher carboxylic acids that have a cross-linked or branched structure may be used in combination with dicarboxylic acids. Examples of trivalent carboxylic acids include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.

[0164] As the polycarboxylic acid, a dicarboxylic acid having a sulfonic acid group or a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids.

[0165] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0166] Examples of the polyol include aliphatic diols (e.g., linear aliphatic diols having a main chain portion with 7 to 20 carbon atoms). Examples of the aliphatic diol include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanediol. Among these, preferred aliphatic diols include 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol.

[0167] Regarding the polyol, a trivalent or higher alcohol having a cross-linked structure or a branched structure may be used in combination with the diol. Examples of the trivalent or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol.

[0168] The polyols may be used alone or in combination of two or more.

[0169] Here, regarding the polyol, for example, the content of the aliphatic diol is preferably 80 mol% or more, and more preferably 90 mol% or more.

[0170] The melting temperature of the crystalline polyester resin is, for example, preferably 50° C. or higher and 100° C. or lower, more preferably 55° C. or higher and 90° C. or lower, and further preferably 60° C. or higher and 85° C. or lower.

[0171] The melting temperature is determined based on the “melting peak temperature” described in the method for determining the melting temperature in JIS K7121-1987 “Methods for determining transition temperatures of plastics” from a DSC curve obtained by differential scanning calorimetry (DSC).

[0172] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably, for example, 6,000 or more and 35,000 or less.

[0173] Similar to the amorphous polyester resin, the crystalline polyester resin can be obtained by, for example, a well-known production method.

[0174] The content of the binder resin is, for example, preferably 40 mass % to 95 mass % inclusive, more preferably 50 mass % to 90 mass % inclusive, and further preferably 60 mass % to 85 mass % inclusive, based on the entire toner particles.

[0175] -Colorant-

[0176] Examples of the colorant include carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, vulcan orange, magenta carmine, permanent red, brilliant carmine 3B, brilliant carmine 6B, Dupont Oil Red, pyrazolone red, litho red, rhodamine B Lake, Red Lake C, pigment red, rose Bengal, aniline blue, ultramarine blue, copper oil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate; and various dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, nigrosine-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based dyes.

[0177] The coloring agents may be used alone or in combination of two or more.

[0178] Here, carbon black, a colorant, is conductive. If the crystalline polyester resin domains grow, conductive paths are likely to form between the carbon black and the crystalline polyester resin, particularly within the toner particles. This results in reduced transferability, which can appear as transfer unevenness in the resulting image.

[0179] However, even if carbon black is used as a colorant in the toner according to this embodiment, conductive paths are less likely to be formed inside the toner particles, and thus transfer unevenness is suppressed.

[0180] The colorant may be a surface-treated colorant as needed, and may be used in combination with a dispersant. Furthermore, multiple colorants may be used in combination.

[0181] The content of the colorant is, for example, preferably 1 mass % or more and 30 mass % or less, and more preferably 3 mass % or more and 15 mass % or less, based on the total mass of the toner particles.

[0182] -Release agent-

[0183] Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montanic acid esters. The release agent is not limited thereto.

[0184] The melting temperature of the release agent is, for example, preferably 50° C. or higher and 110° C. or lower, and more preferably 60° C. or higher and 100° C. or lower.

[0185] The melting temperature is determined based on the “melting peak temperature” described in the method for determining the melting temperature in JIS K7121-1987 “Determination of Transition Temperatures of Plastics” from a DSC curve obtained by differential scanning calorimetry (DSC).

[0186] The content of the releasing agent is, for example, preferably 1 mass % or more and 20 mass % or less, and more preferably 5 mass % or more and 15 mass % or less, based on the total mass of the toner particles.

[0187] -Internally added cross-linked resin particles-

[0188] Internally added crosslinked resin particles are resin particles contained inside toner particles, and refer to resin particles having a bridge structure between specific atoms in the polymer structure of the resin particles.

[0189] The internally added crosslinked resin particles are particles that exist in the toner particles in a state of being incompatible with the binder resin, for example.

[0190] Examples of internally added crosslinked resin particles include crosslinked resin particles crosslinked by ionic bonds (i.e., ionically crosslinked resin particles) and crosslinked resin particles crosslinked by covalent bonds (i.e., covalently crosslinked resin particles). Among these, internally added crosslinked resin particles are preferably crosslinked resin particles crosslinked by covalent bonds.

[0191] The storage modulus G' of the internally added cross-linked resin particles is 1.0×10 5 Pa or more and 1.0×10 6 Pa or less styrene-(meth)acrylic acid copolymer particles.

[0192] If the storage modulus G' of the styrene-(meth)acrylic acid copolymer particles as the internally added cross-linked resin particles is less than 1.0×10 5 Pa, the viscosity of the internally added cross-linked resin particles increases, and the internally added cross-linked resin particles adhere and fuse to form aggregates of the internally added cross-linked resin particles, thereby forming a network of the crystalline polyester resin. As a result, transfer unevenness occurs.

[0193] If the storage modulus G' of the styrene-(meth)acrylic acid copolymer particles as the internally added crosslinked resin particles exceeds 1.0×10 6 Pa, the internally added cross-linked resin particles become too hard, which may impair the low-temperature fixing ability of the toner.

[0194] Furthermore, the storage elastic modulus G' of the internally added cross-linked resin particles in the range of 60°C to 100°C is more preferably 2.0×10 5 Pa or more and 8.0×10 5 Below Pa.

[0195] In order to adjust the storage elastic modulus G′ of the styrene-(meth)acrylic acid copolymer particles as the internally added crosslinked resin particles to fall within the above range, for example, the ratio of the styrene-based monomer to the (meth)acrylic acid-based monomer and the crosslinking amount are adjusted.

[0196] The storage modulus G' of the styrene-(meth)acrylic acid copolymer particles as internally added cross-linked resin particles is measured as follows.

[0197] By applying pressure to the internally added cross-linked resin particles to be measured, a disc-shaped sample with a thickness of 2 mm and a diameter of 8 mm is prepared and used as the measurement sample. Alternatively, when measuring the internally added cross-linked resin particles contained in toner particles, the internally added cross-linked resin particles are removed from the toner particles to prepare the measurement sample. Examples of methods for removing the internally added cross-linked resin particles from toner particles include immersing the toner particles in a solvent that dissolves the binder resin but not the internally added cross-linked resin particles, dissolving the binder resin in the solvent, and then removing the internally added cross-linked resin particles.

[0198] The obtained disc-shaped sample, serving as a measurement sample, was then sandwiched between parallel plates with a diameter of 8 mm. Dynamic viscoelasticity measurements were performed under the following conditions, with the measurement temperature raised from 10°C to 150°C at a rate of 2°C / min at a strain of 0.1 to 100%. The storage modulus G' was determined from the storage modulus curves obtained from the measurements.

[0199] -Measurement conditions-

[0200] Measuring device: Rheometer ARES-G2 (manufactured by TA Instruments)

[0201] Gap: Adjust to 3mm

[0202] Frequency: 1Hz

[0203] The styrene-(meth)acrylic acid copolymer particles as the internally added cross-linked resin particles are particles containing, for example, 50% by mass or more of a styrene-(meth)acrylic acid copolymer as a main component, preferably 80% by mass or more, more preferably 90% by mass or more, and especially substantially all of the styrene-(meth)acrylic acid copolymer in the resin particles.

[0204] The total amount of the styrene-based monomer and the (meth)acrylic-based monomer as monomers constituting the copolymer is preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 95% by mass or more, with the remainder being the crosslinking agent described below.

[0205] Examples of the styrene-(meth)acrylic acid-based copolymer include resins obtained by polymerizing the following styrene-based monomers and (meth)acrylic acid-based monomers by radical polymerization.

[0206] Examples of the styrene-based monomer include styrene, α-methylstyrene, vinylnaphthalene, alkyl-substituted styrenes having an alkyl chain such as 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, and 4-ethylstyrene, halogen-substituted styrenes such as 2-chlorostyrene, 3-chlorostyrene, and 4-chlorostyrene, and fluorine-substituted styrenes such as 4-fluorostyrene and 2,5-difluorostyrene. Among these, styrene and α-methylstyrene are preferred.

[0207] Examples of the (meth)acrylic acid monomer include (meth)acrylic acid, n-methyl (meth)acrylate, n-ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isoamyl (meth)acrylate, and (meth)acrylate. Examples of the present invention include pentyl (meth)acrylate, neopentyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, tert-butylphenyl (meth)acrylate, terphenyl (meth)acrylate, cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-carboxyethyl (meth)acrylate, (meth)acrylonitrile, and (meth)acrylamide. Among these, for example, n-butyl (meth)acrylate and 2-carboxyethyl (meth)acrylate are preferred.

[0208] In the internally added cross-linked resin particles, examples of the cross-linking agent for cross-linking the resin include aromatic polyvinyl compounds such as divinylbenzene and divinylnaphthalene; polyvinyl esters of aromatic polycarboxylic acids such as divinyl phthalate, divinyl isophthalate, divinyl terephthalate, divinyl homophthalate, divinyl trimesic acid, trivinyl trimesic acid, divinyl naphthalate, and divinyl biphenylcarboxylate; divinyl esters of nitrogen-containing aromatic compounds such as divinyl pyridinedicarboxylate; vinyl esters of unsaturated heterocyclic carboxylic acid compounds such as vinyl pyromucate, vinyl furancarboxylate, vinyl pyrrole-2-carboxylate, and vinyl thiophenecarboxylate; butanediol diacrylate, butanediol dimethacrylate, hexanediol diacrylate, hexanediol dimethacrylate, octanediol diacrylate, octanediol dimethacrylate, nonanediol diacrylate, nonanediol dimethacrylate, decanediol di ...acrylate, decanediol diacrylate, decanediol dimethacrylate, decanediol diacrylate, de (Meth)acrylates of linear polyols such as glycol dimethacrylate, dodecanediol diacrylate, and dodecanediol dimethacrylate; (meth)acrylates of branched and substituted polyols such as neopentyl glycol dimethacrylate, 2-hydroxy, and 1,3-diacryloxypropane; polyethylene glycol di(meth)acrylate, polypropylene polyethylene glycol di(meth)acrylates, divinyl succinate, divinyl fumarate, vinyl maleate, and divinyl maleate , divinyl diglycolate, vinyl itaconate, divinyl itaconate, divinyl acetone dicarboxylate, divinyl glutarate, divinyl 3,3'-thiodipropionate, trans-aconitic acid divinyl ester, trans-aconitic acid trivinyl ester, divinyl adipate, divinyl pimelate, divinyl suberate, divinyl azelate, divinyl sebacate, divinyl dodecanedioate, tridecane divinyl ester and the like. The cross-linking agent may be used alone or in combination of two or more.

[0209] Among these, bifunctional alkyl acrylates having an alkylene chain with 6 or more carbon atoms are preferably used as crosslinking agents for crosslinking the resin. That is, the internally added crosslinked resin particles preferably have bifunctional alkyl acrylates as structural units, and the alkylene chain in the bifunctional alkyl acrylate has 6 or more carbon atoms.

[0210] By using internally added crosslinked resin particles having a bifunctional alkyl acrylate as a structural unit and an alkylene chain having 6 or more carbon atoms, a toner can be easily obtained that exhibits appropriate toner deformation during fixing and exhibits particularly good low-temperature fixability. While the internally added crosslinked resin particles have a high crosslink density (i.e., a short distance between crosslinks), their elasticity tends to be excessively high. In contrast, using a bifunctional acrylate having a long alkylene chain as a crosslinking agent results in a low crosslink density (i.e., a long distance between crosslinks), which can prevent the elasticity of the internally added crosslinked resin particles from becoming excessively high.

[0211] From the viewpoint of adjusting the crosslinking density within an appropriate range, the number of carbon atoms in the alkylene chain in the bifunctional alkyl acrylate is, for example, preferably 6 or more, more preferably 6 or more and 12 or less, and even more preferably 8 or more and 12 or less. More specific examples of the bifunctional alkyl acrylate include 1,6-hexanediol acrylate, 1,6-hexanediol methacrylate, 1,8-octanediol diacrylate, 1,8-octanediol dimethacrylate, 1,9-nonanediol diacrylate, 1,9-nonanediol dimethacrylate, 1,10-decanediol diacrylate, 1,10-decanediol dimethacrylate, 1,12-dodecanediol diacrylate, and 1,12-dodecanediol dimethacrylate. Among them, 1,10-decanediol diacrylate and 1,10-decanediol dimethacrylate are preferred.

[0212] As another crosslinking agent, for example, 2-carboxyethyl acrylate can be mentioned, and it is preferable to use at least one of the above-mentioned bifunctional alkyl acrylate and 2-carboxyethyl acrylate.

[0213] In addition, the fixing properties of the styrene-(meth)acrylic acid copolymer particles as internally added crosslinked resin particles can be controlled by adjusting the amount of crosslinking agent contained in the composition. For example, by increasing the amount of crosslinking agent contained in the composition, internally added crosslinked resin particles with good fixing properties can be easily obtained. The content of the crosslinking agent in the composition for forming the internally added crosslinked resin particles is preferably 0.3 parts by mass or more and 5.0 parts by mass or less, more preferably 0.5 parts by mass or more and 3.0 parts by mass or less, and even more preferably 0.8 parts by mass or more and 2.5 parts by mass or less, relative to 100 parts by mass of the total of the styrene monomer, the (meth)acrylic acid monomer, and the crosslinking agent.

[0214] The glass transition temperature Tg(E) of the internally added cross-linked resin particles is, for example, preferably 10° C. or higher and 40° C. or lower, and more preferably 15° C. or higher and 35° C. or lower.

[0215] The method for measuring the glass transition temperature Tg(E) of the internally added cross-linked resin particles is as follows.

[0216] By applying pressure to the internally added cross-linked resin particles to be measured, a disc-shaped sample with a thickness of 2 mm and a diameter of 8 mm is prepared and used as the measurement sample. Alternatively, when measuring the internally added cross-linked resin particles contained in toner particles, the internally added cross-linked resin particles are removed from the toner particles to prepare the measurement sample. Examples of methods for removing the internally added cross-linked resin particles from toner particles include immersing the toner particles in a solvent that dissolves the binder resin but not the internally added cross-linked resin particles, dissolving the binder resin in the solvent, and then removing the internally added cross-linked resin particles.

[0217] The obtained disc-shaped sample, serving as the measurement sample, was then sandwiched between parallel plates with a diameter of 8 mm. Dynamic viscoelasticity measurements were performed under the following conditions, with the temperature raised from 10°C to 150°C at a rate of 2°C / min at a strain of 0.1 to 100%. The loss tangent (tanδ) at each temperature was determined from the loss modulus curve obtained from the measurement. The peak temperature of the loss tangent (tanδ) was then used as the glass transition temperature (Tg(E)) of the internally added crosslinked resin particles.

[0218] -Measurement conditions-

[0219] Measuring device: Rheometer ARES-G2 (manufactured by TA Instruments)

[0220] Gap: Adjust to 3mm

[0221] Frequency: 1Hz

[0222] In the internally added cross-linked resin particles, when the glass transition temperature determined by the Fox equation based on the ratio (mass ratio) of the constituent monomers of the styrene-(meth)acrylic acid copolymer in the entire resin particle is Tg1, and the glass transition temperature determined by the Fox equation based on the ratio (mass ratio) of the constituent monomers of the styrene-(meth)acrylic acid copolymer calculated based on surface analysis of the resin particle is Tg2, the following formulas (T11) and (T21) are preferably satisfied, and the following formulas (T12) and (T22) are more preferably satisfied. This improves low-temperature fixing properties.

[0223] Formula (T11): 5℃<Tg2-Tg1<40℃

[0224] Formula (T12): 10℃<Tg2-Tg1<35℃

[0225] Formula (T21): 100℃>Tg2>10℃

[0226] Formula (T22): 90℃>Tg2>10℃

[0227] Here, the difference between the glass transition temperatures Tg1 and Tg2 based on the Fox equation is believed to indicate that the styrene-based monomer and the (meth)acrylic monomer are not randomly bonded, but rather that there is a mixture of an arrangement where the styrene-derived component is predominant and localized on the particle surface, and an arrangement where the (meth)acrylic-based component is predominant and localized within the particle interior. Specifically, the glass transition temperature of polystyrene resin is approximately 100°C, while the glass transition temperature of (meth)acrylic resin is generally lower than this temperature, for example, approximately -20°C for polyethyl acrylate. Therefore, it is believed that regions rich in styrene-based units are unevenly distributed on the surface of the internally added cross-linked resin particles.

[0228] The ratio of the constituent monomers of the styrene-(meth)acrylate copolymer in the entire resin particles was quantitatively determined by NMR analysis.

[0229] The ratio of the constituent monomers of the styrene-(meth)acrylate copolymer calculated from the surface analysis of the resin particles was quantitatively determined by the following measurement.

[0230] The resin particles were dried and surface composition analysis was performed using an X-ray photoelectron spectroscopy (XPS) apparatus. A JPS-9000MX manufactured by JEOL Ltd. was used as the XPS measuring apparatus. MgKα radiation was used as the X-ray source, with an accelerating voltage of 10 kV and an emission current of 30 mA. The ratio O(p) of oxygen in the resin particles relative to the total of carbon and oxygen was calculated using the following formula.

[0231] O(p) = number of oxygen elements / (number of carbon elements + number of oxygen elements)

[0232] Furthermore, a resin composed only of (meth)acrylate was prepared, and the ratio O(a) of the oxygen element in the (meth)acrylate was determined in the same manner.

[0233] From these measurement results, when the sum of styrene and (meth)acrylate is set to 1, the surface (meth)acrylate ratio Wa(S) and the surface styrene ratio Wb(S) can be calculated by the following formulae.

[0234] Wa(S)=O(p) / O(a)

[0235] Wb(S)=1-(O(p) / O(a))

[0236] Then, the glass transition temperatures Tg1 and Tg2 were calculated using the Fox equation based on the ratio of each constituent monomer determined above.

[0237] When the glass transition temperature of the homopolymer of the (meth)acrylic monomer is TgA (K), the (meth)acrylic monomer ratio (mass ratio: mass %) is WA, the glass transition temperature of the homopolymer of the styrene monomer is TgS (K), and the styrene monomer ratio (mass ratio: mass %) is WS, the following Fox equation holds true for the target glass transition temperature Tg0 (K).

[0238] Fox formula: 1 / Tg0=(WA / TgA)+(WS / TgS)

[0239] Substitute the glass transition temperature and ratio of each (meth)acrylic monomer in the entire resin particle or on the surface of the resin particle, and the glass transition temperature and ratio of the styrene monomer into the Fox equation, and calculate T0 = "target glass transition temperature Tg1 or Tg2" using the Fox equation.

[0240] In addition, as the glass transition temperature of the homopolymer of the (meth)acrylic acid-based monomer and the glass transition temperature of the homopolymer of the styrene-based monomer, either a measured value or a catalog value may be used.

[0241] In the internally added cross-linked resin particles composed of a styrene-(meth)acrylic acid copolymer, the adjustment of Tg(E), Tg1, Tg2, etc. can be achieved by adjusting the polymerization conditions of the copolymer.

[0242] In particular, in order to obtain resin particles having a composition gradient within the internally added cross-linked resin particles and having regions with a high number of styrene units unevenly present on the surface, when manufacturing the particles by polymerization of a monomer solution containing a styrene monomer and a (meth)acrylic monomer, it is preferred that, for example, the content ratio of the styrene monomer relative to the (meth)acrylic monomer in the monomer solution be increased as the polymerization proceeds. "Increasing as the polymerization proceeds" typically means gradually increasing the content ratio of the styrene monomer in the monomer solution, but also includes operations such as gradually increasing the styrene monomer content in the additional monomer when adding additional monomer to the monomer solution in multiple batches, or gradually increasing the styrene monomer concentration in the monomer solution by increasing the amount of additional styrene monomer. For example, when preparing a styrene-(meth)acrylic copolymer by emulsion polymerization, the styrene monomer content in the emulsion can be gradually increased by adding the emulsion multiple times.

[0243] Furthermore, the progress of the reaction can be controlled by adjusting the polymerization temperature, polymerization time, the method of adding the polymerization initiator, and the like.

[0244] The content of the internally added crosslinked resin particles relative to the entire toner is, for example, preferably 2 mass % or more and 20 mass % or less, and more preferably 5 mass % or more and 15 mass % or less.

[0245] By keeping the content of the internally added crosslinked resin particles within the above range, domain growth of the crystalline polyester resin can be easily suppressed. As a result, transfer unevenness can be easily suppressed. In addition, low-temperature fixing properties are improved.

[0246] Here, the mass ratio Wb / Wa of the amorphous polyester resin content Wa to the internally added crosslinked resin particle content Wb relative to the toner particles is, for example, preferably 0.05 to 0.50, more preferably 0.10 to 0.35, and even more preferably 0.12 to 0.30.

[0247] When the ratio Wb / Wa is within the above range, domain growth of the crystalline polyester resin can be easily suppressed. As a result, transfer unevenness can be easily suppressed.

[0248] The mass ratio Wb / Wc of the crystalline polyester resin content Wc to the internally added crosslinked resin particle content Wb relative to the toner particles is, for example, preferably 0.50 to 2.00, more preferably 0.50 to 1.00, and even more preferably 0.60 to 0.80.

[0249] When the ratio Wb / Wc is within the above range, domain growth of the crystalline polyester resin can be easily suppressed. As a result, transfer unevenness can be easily suppressed.

[0250] The average dispersion diameter of the internally added cross-linked resin particles is, for example, preferably from 100 nm to 300 nm, and more preferably from 120 nm to 250 nm.

[0251] When the average dispersion diameter of the internally added cross-linked resin particles is within the above range, domain growth of the crystalline polyester resin is easily suppressed. As a result, transfer unevenness is easily suppressed and low-temperature fixing properties are improved.

[0252] The method for measuring the average dispersion diameter of the internally added cross-linked resin particles is as follows.

[0253] The toner particles or toner are mixed with epoxy resin and embedded to solidify the epoxy resin. The obtained solidified material is cut using an ultrathin sectioning device (Ultracut UCT manufactured by Leica) to produce a thin sheet sample having a thickness of more than 80 nm and less than 130 nm. Next, the obtained thin sheet sample is stained with ruthenium tetroxide in a desiccator at 30°C for 3 hours. Then, an SEM image of the stained thin sheet sample is obtained using an ultra-high resolution field emission scanning electron microscope (FE-SEM, manufactured by Hitachi High-Technologies Corporation, S-4800). Since the ease of staining with ruthenium tetroxide is different in the order of release agent, styrene-(meth) acrylic resin, and polyester resin, each component is identified based on the depth caused by the degree of staining. If it is difficult to distinguish the depth based on the state of the sample, the staining time is adjusted.

[0254] In addition, in the cross section of the toner particles, the domains of the colorant are smaller than the domains of the release agent and the domains of the resin particles, and thus can be distinguished based on their size.

[0255] In the SEM image, 30 toner cross sections with a maximum length of at least 85% of the toner particle volume average particle diameter were selected, and a total of 100 dyed internally added cross-linked resin particles (i.e., their domains) were observed. The maximum length of each domain was measured, and the maximum length was considered the domain diameter. The average equivalent circle diameter was calculated by arithmetic averaging these diameters. The obtained average equivalent circle diameter was then used as the average dispersed diameter of the internally added cross-linked resin particles.

[0256] The adjustment of the average dispersion diameter of the internally added cross-linked resin particles can be achieved, for example, by controlling the following steps: producing toner particles by agglomeration, adjusting the volume average particle size of the internally added cross-linked resin particles contained in the internally added cross-linked resin particle dispersion used during the production; preparing a plurality of internally added cross-linked resin particle dispersions having different volume average particle sizes and using them in combination.

[0257] The average shape factor SF-1 of the internally added cross-linked resin particles is preferably 130 or less, for example.

[0258] When the average shape factor SF-1 of the internally added cross-linked resin particles is within the above range, domain growth of the crystalline polyester resin is easily suppressed. As a result, transfer unevenness is easily suppressed and low-temperature fixing properties are improved.

[0259] The average shape factor SF-1 was calculated by the following formula.

[0260] SF-1=(ML / A)×(π / 4)×100

[0261] In the above formula, ML represents the absolute maximum length of the toner particle, and A represents the projected area of ​​the toner particle.

[0262] Specifically, a sample was prepared using the same method as described above for measuring the average dispersion diameter of the internally added cross-linked resin particles. Thirty toner cross-sections with a maximum length of at least 85% of the toner particle volume average particle diameter were selected for SEM imaging, and a total of 100 dyed internally added cross-linked resin particles were observed. The observed SEM images were read into the Luzex image analysis and processing system (manufactured by NIRECO CORPORATION). The maximum length and projected area of ​​the 100 particles were calculated and averaged using the above formula. This average was used as the average shape factor SF-1 of the internally added cross-linked resin particles.

[0263] -Method for producing internally added cross-linked resin particles-

[0264] As a method for producing internally added cross-linked resin particles, for example, known methods such as emulsion polymerization, melt kneading using a Banbury mixer or kneader, suspension polymerization, and spray drying can be used. However, in order to make the units derived from the styrene-based monomers unevenly present on the particle surface, emulsion polymerization is preferred.

[0265] In the method for producing internally added crosslinked resin particles, for example, it is preferred to use a styrene-based monomer and a (meth)acrylic-based monomer as monomers and polymerize them in the presence of a crosslinking agent.

[0266] In the method for producing internally added crosslinked resin particles, for example, it is preferable to carry out emulsion polymerization multiple times.

[0267] Hereinafter, the method for producing the internally added cross-linked resin particles will be described in more detail.

[0268] The method for producing internally added cross-linked resin particles preferably includes, for example:

[0269] a step of obtaining an emulsion containing a monomer, a cross-linking agent, a surfactant, and water (emulsion preparation step);

[0270] a step of polymerizing the monomers by adding a polymerization initiator to the emulsion and heating the emulsion (a first emulsion polymerization step); and

[0271] A step of polymerizing the monomer by adding an emulsion containing a monomer and a cross-linking agent to the reaction solution after the first emulsion polymerization step and heating the mixture (second emulsion polymerization step).

[0272] Furthermore, in the second emulsion polymerization step, in order to adjust the composition of the particle surface, the ratio of the styrene-based monomer to the (meth)acrylic-based monomer may be changed to prepare an emulsion, and then the emulsion may be added multiple times.

[0273] --Emulsion preparation process--

[0274] This is a step of obtaining an emulsion containing monomers, a crosslinking agent, a surfactant, and water.

[0275] For example, it is preferred to obtain an emulsion by emulsifying a monomer, a crosslinking agent, a surfactant, and water using an emulsifier.

[0276] Examples of emulsifiers include rotary stirrers with propeller-type, anchor-type, paddle-type, or turbine-type stirring blades; static mixers such as static mixers; rotor / stator emulsifiers such as homogenizers and CERAMIX; mill-type emulsifiers with a grinding function; high-pressure emulsifiers such as a Manton-Gaulin pressure emulsifier; high-pressure nozzle-type emulsifiers that generate cavitation under high pressure; high-pressure collision-type emulsifiers such as a microfluidizer that apply shear force by causing liquids to collide with each other under high pressure; ultrasonic emulsifiers that generate cavitation using ultrasonic waves; membrane emulsifiers that emulsify through fine pores, etc.

[0277] As the monomer, for example, a styrene-based monomer and a (meth)acrylic-based monomer are preferably used.

[0278] As the cross-linking agent, the cross-linking agents already described are suitable.

[0279] Examples of surfactants include anionic surfactants such as sulfate esters, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols. Nonionic surfactants can be used in combination with anionic or cationic surfactants. Among these, anionic surfactants are preferred. Surfactants can be used alone or in combination of two or more.

[0280] The emulsion may contain a chain transfer agent. As the chain transfer agent, there is no particular limitation, and compounds having a mercaptan component can be used. Specifically, for example, alkyl mercaptans such as hexyl mercaptan, heptyl mercaptan, octyl mercaptan, nonyl mercaptan, decyl mercaptan, and dodecyl mercaptan are preferred.

[0281] The mass ratio of the styrene-based monomer to the (meth)acrylic-based monomer in the emulsion (styrene-based monomer / (meth)acrylic-based monomer) is preferably, for example, 0.2 or more and 1.1 or less.

[0282] Furthermore, the content of the cross-linking agent relative to the entire emulsion is preferably, for example, 0.5% by mass or more and 3% by mass or less.

[0283] --First emulsion polymerization step--

[0284] This is a step of adding a polymerization initiator to the emulsion and heating it to polymerize the monomers.

[0285] Here, when performing polymerization, it is preferred that the emulsion (reaction solution) containing the polymerization initiator is stirred using, for example, a stirrer.

[0286] Examples of the stirrer include a rotary stirrer equipped with a propeller-type, anchor-type, paddle-type, or turbine-type stirring blade.

[0287] As the polymerization initiator, for example, ammonium persulfate is preferably used.

[0288] --Second emulsion polymerization step--

[0289] This is a step of polymerizing the monomers by adding an emulsion containing the monomers to the reaction solution after the first emulsion polymerization step and heating the mixture.

[0290] During the polymerization, for example, the reaction solution is preferably stirred in the same manner as in the first emulsion polymerization step.

[0291] In this step, the ratio of the styrene-based monomer to the (meth)acrylic-based monomer in the emulsion containing monomers may be changed, and the emulsion may be added in multiple batches.

[0292] The emulsion containing the monomer is preferably obtained by emulsifying the monomer, a surfactant, and water using an emulsifier, for example.

[0293] -Other additives-

[0294] Examples of other additives include well-known additives such as magnetic materials, charge control agents, and inorganic powders. These additives are contained in the toner particles as internal additives.

[0295] - Characteristics of toner particles, etc. -

[0296] The toner particles may be toner particles of a single-layer structure, or may be toner particles of a so-called core-shell structure composed of a core (core particle) and a coating layer (shell layer) that covers the core.

[0297] Here, the core-shell toner particles preferably include, for example, a core portion containing a binder resin, internally added crosslinked resin particles, and optionally other additives such as a colorant and a release agent, and a coating layer containing a binder resin and internally added crosslinked resin particles.

[0298] The volume average particle diameter (D50v) of the toner particles is, for example, preferably 2 μm or more and 10 μm or less, and more preferably 4 μm or more and 8 μm or less.

[0299] Various average particle sizes and various particle size distribution indices of the toner particles are measured using Coulter Multisizer II (manufactured by Beckman Coulter) and ISOTON-II (manufactured by Beckman Coulter) as the electrolyte.

[0300] During measurement, 0.5 mg to 50 mg of a sample is added to 2 ml of a 5% aqueous solution of a surfactant (e.g., preferably sodium alkylbenzenesulfonate) as a dispersant, and this is added to 100 ml to 150 ml of the electrolyte.

[0301] The electrolyte solution containing the sample was dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with a diameter of 2 μm to 60 μm was measured using a Coulter Multisizer II with a pore diameter of 100 μm. 50,000 particles were sampled.

[0302] For the particle size range (interval) divided based on the particle size distribution to be measured, the volume cumulative distribution and the number cumulative distribution are respectively drawn from the smaller diameter side, and the particle size that will become 16% of the cumulative is defined as the volume particle size D16v and the number particle size D16p, the particle size that will become 50% of the cumulative is defined as the volume average particle size D50v and the cumulative number average particle size D50p, and the particle size that will become 84% of the cumulative is defined as the volume particle size D84v and the number particle size D84p.

[0303] Use these, by (D84v / D16v) 1 / 2 Calculate the volume particle size distribution index (GSDv) by (D84p / D16p) 1 / 2 Calculate the particle size distribution index (GSDp).

[0304] The average circularity of the toner particles is, for example, preferably 0.90 or more and 1.00 or less, and more preferably 0.92 or more and 0.98 or less.

[0305] The average circularity of the toner particles is calculated as (circle-equivalent circumference) / (circumference) [(circumference of a circle having the same projected area as the particle image) / (circumference of the particle projected image)]. Specifically, it is a value measured by the following method.

[0306] First, the toner particles to be measured were collected by suction, forming a flattened flow. This flow was then momentarily stroboscoped to capture a particle image as a still image. This particle image was then analyzed using a flow particle image analyzer (FPIA-3000, manufactured by Sysmex Corporation). The average circularity was determined using a sample count of 3500.

[0307] When the toner contains an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant and then subjected to ultrasonic treatment to obtain toner particles from which the external additive has been removed.

[0308] (External additives)

[0309] Examples of external additives include inorganic particles. Examples of inorganic particles include SiO2, TiO2, Al2O3, SrTiO3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2) n , Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4 and other particles.

[0310] As the surface of the inorganic particles of the external additive, for example, hydrophobization treatment is preferably implemented.Hydrophobic treatment is carried out, for example, by impregnating the inorganic particles in a hydrophobization treatment agent.The hydrophobization treatment agent is not particularly limited, and for example, silane coupling agents, silicone oils, titanate coupling agents, aluminum coupling agents, etc. can be cited. They can be used alone or in combination of two or more.

[0311] The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the inorganic particles.

[0312] Examples of external additives include resin particles (polystyrene, polymethyl methacrylate (PMMA), melamine resin, and the like), cleaning activators (for example, metal salts of higher fatty acids such as zinc stearate, and particles of fluorine-based high molecular weight substances).

[0313] The amount of the external additive added is, for example, preferably 0.01% by mass or more and 10% by mass or less, and more preferably 0.01% by mass or more and 6.0% by mass or less, based on the toner particles.

[0314] (Dielectric loss factor of toner)

[0315] In the toner according to this embodiment, the dielectric loss coefficient of the toner at 1 kHz after being left at a temperature of 28° C. and a relative humidity of 85% RH is preferably 35×10 -3 Below, more preferably 30×10 -3 the following.

[0316] If the dielectric loss factor of the toner according to this embodiment is within the above range, the excessive growth of numerous crystalline polyester resin domains prevents the formation of conductive paths within the toner particles. Therefore, even when the water content of the toner particles increases in high-temperature and high-humidity environments, charge injection properties are less likely to deteriorate. Consequently, transfer unevenness is easily suppressed even in high-temperature and high-humidity environments.

[0317] The dielectric loss coefficient of the toner can be adjusted by the contents of the crystalline polyester resin particles and the internally added cross-linked resin particles, the glass transition temperature Tg(E) of the internally added cross-linked resin particles, and the like.

[0318] Here, the dielectric loss coefficient of toner is explained. First, the dielectric loss tangent (tanδ) is expressed as the ratio of the real part ε' to the imaginary part ε" in the complex dielectric constant ε = ε'-iε" (i is an imaginary unit), and is expressed as dielectric loss tangent (tanδ) = ε" / ε'. The imaginary part ε" is called the dielectric loss coefficient.

[0319] The dielectric loss factor of the toner is measured as follows.

[0320] 6 g of the toner to be measured was weighed and allowed to stand in an environment of 28°C and 85% relative humidity for at least 3 hours. A load of 10 tons was then applied for 1 minute to form pellets. The resulting pellets were again allowed to stand in an environment of 28°C and 85% relative humidity for at least 1 hour. The pellets were then placed between electrodes with a diameter of 3.8 cm and the dielectric loss coefficient of the toner was measured using an LCR meter (LCR meter model 6440A, manufactured by TOYO CORPORATION) at 25°C, 50% RH, a frequency of 1 kHz, and a voltage of 5 V.

[0321] (Toner Manufacturing Method)

[0322] Next, a method for producing a toner according to this embodiment will be described.

[0323] The toner according to this embodiment is obtained by manufacturing toner particles and then adding an external additive to the toner particles.

[0324] Toner particles can be produced by any of dry methods (e.g., kneading and pulverization methods) or wet methods (e.g., coagulation, suspension polymerization, and dissolution suspension methods). The method for producing toner particles is not particularly limited to these methods, and well-known methods may also be used.

[0325] Among these, for example, it is preferable to obtain toner particles by an aggregation method.

[0326] Specifically, for example, when toner particles are produced by an aggregation method, the toner particles are produced through the following steps:

[0327] a step of mixing a first amorphous resin particle dispersion containing first amorphous resin particles as a binder resin, a crystalline resin particle dispersion containing crystalline resin particles as a binder resin, an internally added crosslinked resin particle dispersion containing internally added crosslinked resin particles, a colorant dispersion containing a colorant, and a release agent particle dispersion containing particles of a release agent (hereinafter also referred to as "release agent particles"), and aggregating the particles and the colorant in the obtained dispersion to form first aggregated particles (a first aggregated particle forming step);

[0328] After obtaining a first aggregated particle dispersion in which first aggregated particles are dispersed, second amorphous resin particles serving as a binder resin are added to the first aggregated particle dispersion to aggregate the second amorphous resin particles on surfaces of the first aggregated particles to form second aggregated particles (a second aggregated particle forming step); and

[0329] A step of heating the second aggregated particle dispersion in which the second aggregated particles are dispersed to fuse and unify the second aggregated particles to form toner particles (fusing and unifying step).

[0330] Here, amorphous polyester resin particles are suitable as the first and second amorphous resin particles, crystalline polyester resin particles are suitable as the crystalline resin particles, and styrene-(meth)acrylic acid copolymer particles are suitable as the internally added crosslinked resin particles.

[0331] Furthermore, although the present aggregation method is described as a method for producing toner particles containing a binder resin, a colorant, and a release agent, the colorant and the release agent are components contained in the toner particles as necessary.

[0332] Hereinafter, the details of each step will be described.

[0333] -Dispersion Preparation Steps-

[0334] First, various dispersions used in the cohesion method are prepared. Specifically, a first amorphous resin particle dispersion containing first amorphous resin particles as a binder resin, a crystalline resin particle dispersion containing crystalline resin particles, an internally added crosslinked resin particle dispersion containing internally added crosslinked resin particles, a colorant dispersion containing a colorant, a second amorphous resin particle dispersion containing second amorphous resin particles as a binder resin, and a release agent particle dispersion containing release agent particles are prepared.

[0335] In addition, in each dispersion preparation step, the first amorphous resin particles, the second amorphous resin particles, and the crystalline resin particles are referred to as “resin particles” in the description.

[0336] Here, the resin particle dispersion is prepared by, for example, dispersing the resin particles in a dispersion medium using a surfactant.

[0337] Examples of the dispersion medium used for the resin particle dispersion include aqueous media.

[0338] Examples of the aqueous medium include water such as distilled water and ion-exchanged water, and alcohols, etc. These may be used alone or in combination of two or more.

[0339] Examples of surfactants include anionic surfactants such as sulfate esters, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols. Among these, anionic surfactants and cationic surfactants are particularly useful. Nonionic surfactants can be used in combination with anionic or cationic surfactants.

[0340] The surfactant may be used alone or in combination of two or more.

[0341] In a resin particle dispersion, the resin particles may be dispersed in a dispersion medium using, for example, a general dispersion method such as a rotary shearing homogenizer, a ball mill equipped with media, a sand mill, or a dyno-mill. Depending on the type of resin particles, the resin particles may be dispersed in the resin particle dispersion using, for example, a phase inversion emulsification method.

[0342] The phase inversion emulsification method refers to a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) for neutralization, and then an aqueous medium (W phase) is added to convert the resin from W / O to O / W (so-called phase inversion) to form a discontinuous phase, thereby dispersing the resin into particles in the aqueous medium.

[0343] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably 0.01 μm or more and 1 μm or less, more preferably 0.08 μm or more and 0.8 μm or less, and further preferably 0.1 μm or more and 0.6 μm or less.

[0344] The volume average particle size of the resin particles is determined by dividing the particle size distribution obtained by measurement using a laser diffraction particle size distribution analyzer (e.g., LA-700, manufactured by HORIBA, Ltd.) into the resulting particle size ranges (intervals). The cumulative distribution is plotted toward the smaller particle size side, and the particle size at which the cumulative distribution of all particles reaches 50% is determined as the volume average particle size D50v. The volume average particle size of particles in other dispersions is also measured in the same manner.

[0345] The content of the resin particles in the resin particle dispersion is, for example, preferably 5% by mass or more and 50% by mass or less, and more preferably 10% by mass or more and 40% by mass or less.

[0346] In addition, a colorant dispersion, a release agent particle dispersion, and an internally added crosslinked resin particle dispersion are also prepared in the same manner as the resin particle dispersion. Specifically, the volume average particle size of the particles in the resin particle dispersion, the dispersion medium, the dispersion method, and the particle content are the same for the colorant dispersed in the colorant dispersion, the release agent particles dispersed in the release agent particle dispersion, and the internally added crosslinked resin particles dispersed in the internally added crosslinked resin particle dispersion.

[0347] -First Agglomerated Particle Formation Step-

[0348] Next, the first amorphous resin particle dispersion, the crystalline resin particle dispersion, the internally added crosslinked resin particle dispersion, the colorant dispersion, and the release agent particle dispersion are mixed.

[0349] Then, the first amorphous resin, crystalline resin particles, internally added crosslinked resin particles, colorant and release agent particles are heterogeneously aggregated in the mixed dispersion to form first aggregated particles containing the first amorphous resin, internally added crosslinked resin particles, colorant and release agent particles.

[0350] Specifically, for example, a coagulant is added to a dispersion obtained by mixing a first amorphous resin particle dispersion, a crystalline resin particle dispersion, an internally added cross-linked resin particle dispersion, a colorant dispersion, and a release agent particle dispersion, and the pH of the mixed dispersion is adjusted to be acidic (for example, a pH of 2 or more and 5 or less). After adding a dispersion stabilizer as needed, the temperature is set to a range of 20°C or more and 50°C or less, so that the particles dispersed in the mixed dispersion are agglomerated, thereby forming first agglomerated particles.

[0351] In the first condensed particle formation process, for example, the above-mentioned coagulant can be added at room temperature (for example, 25°C) while stirring the mixed dispersion using a rotary shearing homogenizer, and the pH of the mixed dispersion is adjusted to acidic (for example, pH is greater than 2 and less than 5), and the above-mentioned heating is performed after adding a dispersion stabilizer as needed.

[0352] Examples of coagulants include surfactants with opposite polarity to the surfactant used as a dispersant added to the mixed dispersion, inorganic metal salts, and divalent or higher metal complexes. In particular, when a metal complex is used as a coagulant, the amount of surfactant used is reduced, and the charging characteristics are improved.

[0353] If necessary, an additive that forms a complex or similar bond with the metal ion of the coagulant may be used. As such an additive, a chelating agent may be used.

[0354] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide.

[0355] As the chelating agent, a water-soluble chelating agent can be used. Examples of the chelating agent include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid, iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA).

[0356] The amount of the chelating agent added is preferably 0.01 to 5.0 parts by mass, and more preferably 0.1 to less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles (first amorphous resin particles, crystalline resin particles, and internally added crosslinked resin particles).

[0357] -Second Agglomerated Particle Formation Step-

[0358] Next, after obtaining the first aggregated particle dispersion in which the first aggregated particles are dispersed, the second amorphous resin particle dispersion in which the second amorphous resin particles are dispersed is added to the first aggregated particle dispersion.

[0359] The second amorphous resin particles may be of the same kind as the first amorphous resin or may be of a different kind.

[0360] Next, in a dispersion of the first agglomerated particles and the second amorphous resin particles, the second amorphous resin particles are agglomerated on the surfaces of the first agglomerated particles. At this time, a dispersion of release agent particles may be added to agglomerate the second amorphous resin particles and the release agent particles on the surfaces of the first agglomerated particles. Specifically, for example, in the first agglomerated particle formation step, when the first agglomerated particles have reached a target particle size, the second amorphous resin particle dispersion is added to the first agglomerated particle dispersion, and the mixture is heated below the glass transition temperature of the second amorphous resin particles.

[0361] Then, by adjusting the pH of the dispersion liquid to a range of approximately 6.5 or higher and 8.5 or lower, the aggregation is stopped.

[0362] In this manner, second aggregated particles are obtained in which the second amorphous resin particles are aggregated so as to adhere to the surfaces of the first aggregated particles.

[0363] -Fusion / unification process-

[0364] Next, the second agglomerated particle dispersion in which the second agglomerated particles are dispersed is heated, for example, to a temperature above the glass transition temperature of the first and second amorphous resin particles (for example, a temperature 10 to 30°C higher than the glass transition temperature of the first and second amorphous resin particles) to fuse / unify the second agglomerated particles, thereby forming toner particles.

[0365] Through the above steps, toner particles can be obtained.

[0366] In the above-described aggregation and unification method, the first aggregated particles may be fused and unified to form toner particles without performing the second aggregated particle formation step. Furthermore, the second aggregated particle formation step may be repeated multiple times.

[0367] Furthermore, in the second aggregated particle forming step, a crystalline resin particle dispersion may be used, and an internally added cross-linked resin particle dispersion may also be used.

[0368] Here, after the fusion / unification step is completed, the toner particles formed in the solution are subjected to a known washing step, a solid-liquid separation step, and a drying step to obtain dry toner particles.

[0369] The washing step is not particularly limited, but from the perspective of chargeability, it is preferred to fully perform displacement washing with ion-exchanged water. Furthermore, the solid-liquid separation step is not particularly limited, but from the perspective of productivity, suction filtration, pressure filtration, etc. are preferably performed. Furthermore, the drying method is not particularly limited, but from the perspective of productivity, freeze drying, airflow drying, fluidized bed drying, vibrating fluidized bed drying, etc. are preferably performed.

[0370] The toner according to this embodiment is produced, for example, by adding an external additive to the obtained dry toner particles and mixing them. Mixing is preferably performed using, for example, a V-blender, Henschel mixer, or Lödige mixer. Furthermore, if necessary, a vibrating screen or pneumatic screen can be used to remove coarse toner particles.

[0371] <Electrostatic image developer>

[0372] The electrostatic image developer according to this embodiment includes at least the toner according to this embodiment.

[0373] The electrostatic image developer according to the present embodiment may be a one-component developer containing only the toner according to the present embodiment, or a two-component developer in which the toner and a carrier are mixed.

[0374] The carrier is not particularly limited, and known carriers may be used. Examples of the carrier include coated carriers in which a core material composed of magnetic powder is coated with a coating resin; magnetic powder-dispersed carriers in which magnetic powder is dispersed or blended in a matrix resin; and resin-impregnated carriers in which porous magnetic powder is impregnated with a resin.

[0375] Furthermore, the magnetic powder dispersed carrier and the resin impregnated carrier may be a carrier in which the constituent particles of the carrier serve as a core material and the core material is coated with a coating resin.

[0376] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt, and magnetic oxides such as ferrite and magnetite.

[0377] Examples of the coating resin and matrix resin include styrene-(meth)acrylic resin; polyolefin resins such as polyethylene resin and polypropylene resin; polyvinyl or polyvinylidene resins such as polystyrene, (meth)acrylic resin, polyacrylonitrile, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl carbazole, polyvinyl ether, and polyvinyl ketone; vinyl chloride-vinyl acetate copolymer; linear silicone resin composed of an organic siloxane bond or a modified product thereof; fluororesins such as polytetrafluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, and polychlorotrifluoroethylene; polyester; polyurethane; polycarbonate; amino resins such as urea-formaldehyde resin; epoxy resin, etc.

[0378] The coating resin and the matrix resin preferably contain, for example, a (meth)acrylic resin, more preferably contain 50% by mass or more of the (meth)acrylic resin relative to the total mass of the resin, and even more preferably contain 80% by mass or more of the (meth)acrylic resin relative to the total mass of the resin.

[0379] In particular, the coating resin and the matrix resin preferably contain, for example, an alicyclic (meth)acrylic resin as the (meth)acrylic resin.

[0380] Furthermore, the coating resin and the matrix resin may contain other additives such as conductive particles.

[0381] Examples of the conductive particles include particles of metals such as gold, silver, and copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.

[0382] Here, in order to coat the surface of the core material with a coating resin, a coating method using a coating layer forming solution prepared by dissolving the coating resin and various additives added as needed in an appropriate solvent can be cited. The solvent is not particularly limited and can be selected taking into account the coating resin used, coating suitability, etc.

[0383] Specific resin coating methods include an immersion method in which the core material is immersed in a coating layer forming solution, a spraying method in which the coating layer forming solution is sprayed onto the surface of the core material, a fluidized bed method in which the coating layer forming solution is sprayed while the core material is floating using flowing air, and a kneading coating method in which the core material of the carrier and the coating layer forming solution are mixed in a kneading coater and the solvent is removed.

[0384] The mixing ratio (mass ratio) of the toner and the carrier in the two-component developer is, for example, preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.

[0385] <Image Forming Apparatus / Image Forming Method>

[0386] The image forming apparatus and image forming method according to this embodiment will be described.

[0387] The image forming apparatus according to this embodiment includes: an image holder; a charging device for charging the surface of the image holder; an electrostatic image forming device for forming an electrostatic image on the charged surface of the image holder; a developing device for storing an electrostatic image developer and developing the electrostatic image formed on the surface of the image holder into a toner image using the electrostatic image developer; a transfer device for transferring the toner image formed on the surface of the image holder to the surface of a recording medium; and a fixing device for fixing the toner image transferred to the surface of the recording medium. The electrostatic image developer according to this embodiment is used as the electrostatic image developer.

[0388] In the image forming device involved in this embodiment, an image forming method (the image forming method involved in this embodiment) is implemented, which includes the following processes: a charging process, in which the surface of the image retaining body is charged; an electrostatic image forming process, in which an electrostatic image is formed on the surface of the charged image retaining body; a developing process, in which the electrostatic image formed on the surface of the image retaining body is developed into a toner image using the electrostatic image developer involved in this embodiment; a transfer process, in which the toner image formed on the surface of the image retaining body is transferred to the surface of the recording medium; and a fixing process, in which the toner image transferred to the surface of the recording medium is fixed.

[0389] The image forming device involved in this embodiment is applicable to the following well-known image forming devices: a device of a direct transfer method in which a toner image formed on the surface of an image retaining body is directly transferred to a recording medium; a device of an intermediate transfer method in which a toner image formed on the surface of an image retaining body is transferred to the surface of an intermediate transfer body for the first time, and the toner image transferred to the surface of the intermediate transfer body is transferred to the surface of a recording medium for the second time; a device having a cleaning device for cleaning the surface of the image retaining body after transferring the toner image but before charging; a device having an electrostatic elimination device for eliminating static electricity by irradiating the surface of the image retaining body with electrostatic elimination light after transferring the toner image and before charging, etc.

[0390] In the case of an intermediate transfer method device, the transfer device may, for example, have the following structure: an intermediate transfer body, on the surface of which a toner image is transferred; a primary transfer device, which transfers the toner image formed on the surface of the image retaining body to the surface of the intermediate transfer body for the primary transfer; and a secondary transfer device, which transfers the toner image transferred to the surface of the intermediate transfer body for the secondary transfer to the surface of the recording medium.

[0391] In the image forming apparatus according to the present embodiment, the portion including the developing device may be a cartridge structure (processing cartridge) that is detachably mounted on the image forming apparatus. As the processing cartridge, for example, a processing cartridge including the developing device containing the electrostatic image developer according to the present embodiment may be preferably used.

[0392] Hereinafter, an example of the image forming apparatus according to the present embodiment is shown, but the present invention is not limited thereto. In addition, the main parts shown in the drawings will be described, and the description of the other parts will be omitted.

[0393] Figure 1 FIG. 1 is a diagram schematically showing the configuration of an image forming apparatus according to this embodiment.

[0394] Figure 1 The image forming apparatus shown includes first to fourth electrophotographic image forming units 10Y, 10M, 10C, and 10K that output images in yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged side by side, separated from each other by a predetermined distance in the horizontal direction. Alternatively, these units 10Y, 10M, 10C, and 10K may be process cartridges that are attachable to and detachable from the image forming apparatus.

[0395] An intermediate transfer belt 20, serving as an intermediate transfer member, extends above each unit 10Y, 10M, 10C, and 10K in the drawing. The intermediate transfer belt 20 is wound around a drive roller 22 and a support roller 24, which are arranged to be spaced apart from each other in the left-to-right direction in the drawing, and travels from the first unit 10Y toward the fourth unit 10K. The support roller 24 is biased away from the drive roller 22 by a spring (not shown), thereby applying tension to the intermediate transfer belt 20 wound around the drive roller 22. Furthermore, an intermediate transfer member cleaning device 30 is provided on the outer circumference of the intermediate transfer belt 20, facing the drive roller 22.

[0396] In addition, the toners including the four colors of yellow, magenta, cyan and black contained in the toner cartridges 8Y, 8M, 8C and 8K are supplied to the developing devices (an example of a developing device) 4Y, 4M, 4C and 4K of each unit 10Y, 10M, 10C and 10K respectively.

[0397] The first to fourth units 10Y, 10M, 10C, and 10K have the same structure. Therefore, the first unit 10Y, which forms a yellow image and is located upstream in the direction of travel of the intermediate transfer belt, will be described as a representative unit. Components identical to those of the first unit 10Y will be designated with magenta (M), cyan (C), and black (K) instead of yellow (Y), and the description of the second to fourth units 10M, 10C, and 10K will be omitted.

[0398] The first unit 10Y includes a photoreceptor 1Y, which functions as an image holder. Sequentially arranged around the photoreceptor 1Y are: a charging roller (an example of a charging device) 2Y, which charges the surface of the photoreceptor 1Y to a predetermined potential; an exposure device (an example of an electrostatic image forming device) 3, which exposes the charged surface to a laser beam 3Y based on a color-decomposed image signal to form an electrostatic image; a developing device (an example of a developing device) 4Y, which supplies charged toner to the electrostatic image to develop the electrostatic image; a primary transfer roller (an example of a primary transfer device) 5Y, which transfers the developed toner image to the intermediate transfer belt 20; and a photoreceptor cleaning device (an example of a cleaning device) 6Y, which removes toner remaining on the surface of the photoreceptor 1Y after the primary transfer.

[0399] The primary transfer roller 5Y is disposed inside the intermediate transfer belt 20 and is positioned opposite the photoreceptor 1Y. Furthermore, each of the primary transfer rollers 5Y, 5M, 5C, and 5K is connected to a bias power supply (not shown) for applying a primary transfer bias. Each bias power supply is controlled by a control unit (not shown) to vary the transfer bias applied to each primary transfer roller.

[0400] Next, the operation of forming a yellow image in the first unit 10Y will be described.

[0401] First, before the operation, the surface of the photoreceptor 1Y is charged to a potential of -600 V to -800 V by the charging roller 2Y.

[0402] The photoreceptor 1Y is conductive (e.g., volume resistivity at 20°C: 1×10 -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate (with a resistance of 100 Ω·cm or less). This photosensitive layer typically has a high electrical resistance (the resistance of a typical resin), but when irradiated with laser beam 3Y, the specific electrical resistance of the portion irradiated by the laser beam changes. Therefore, based on yellow image data sent from a control unit (not shown), laser beam 3Y is output via exposure device 3 to the surface of the charged photoreceptor 1Y. Laser beam 3Y irradiates the photosensitive layer on the surface of photoreceptor 1Y, forming an electrostatic image of a yellow image pattern on the surface of photoreceptor 1Y.

[0403] An electrostatic image refers to an image formed on the surface of the photoreceptor 1Y by charging, and is a so-called negative latent image. It is formed by the resistivity of the irradiated portion of the photosensitive layer being reduced by the laser beam 3Y, and the charged charge on the surface of the photoreceptor 1Y flowing, while on the other hand, the charge on the portion not irradiated by the laser beam 3Y remains.

[0404] As the photoreceptor 1Y travels, the electrostatic image formed on the photoreceptor 1Y rotates to a predetermined developing position, where the developing device 4Y converts the electrostatic image on the photoreceptor 1Y into a visible image (developed image) as a toner image.

[0405] The developing device 4Y contains, for example, an electrostatic image developer containing at least yellow toner and a carrier. The yellow toner is triboelectrically charged by being stirred within the developing device 4Y, resulting in a charge of the same polarity (negative) as the charge on the photoreceptor 1Y and being retained on the developer roller (an example of a developer retainer). The surface of the photoreceptor 1Y then passes through the developing device 4Y, whereupon the yellow toner electrostatically adheres to the de-electrostaticized latent image on the surface of the photoreceptor 1Y, thereby developing the latent image with the yellow toner. The photoreceptor 1Y, with the yellow toner image formed on it, continues to travel at a predetermined speed, and the toner image developed on the photoreceptor 1Y is transported to a predetermined primary transfer position.

[0406] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer position, a primary transfer bias is applied to the primary transfer roller 5Y. Electrostatic force from the photoreceptor 1Y toward the primary transfer roller 5Y acts on the toner image, transferring the toner image on the photoreceptor 1Y to the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and is controlled to, for example, +10 μA by a control unit (not shown) in the first unit 10Y.

[0407] On the other hand, the toner remaining on the photoreceptor 1Y is removed and recovered by the photoreceptor cleaning device 6Y.

[0408] Furthermore, the primary transfer bias applied to the primary transfer rollers 5M, 5C, and 5K in and after the second unit 10M is also controlled in accordance with the first unit.

[0409] In this manner, the intermediate transfer belt 20 to which the yellow toner image has been transferred by the first unit 10Y is sequentially transported through the second to fourth units 10M, 10C, and 10K, so that the toner images of the respective colors are superimposed and multi-transferred.

[0410] The intermediate transfer belt 20, to which the four-color toner images have been multiply transferred by the first through fourth units, reaches the secondary transfer section, which is comprised of the intermediate transfer belt 20, a backup roller 24 in contact with the inner surface of the intermediate transfer belt, and a secondary transfer roller (an example of a secondary transfer device) 26 disposed on the outer circumference of the intermediate transfer belt 20. Meanwhile, recording paper (an example of recording medium) P is fed into the gap between the secondary transfer roller 26 and the intermediate transfer belt 20 via a feed mechanism at a predetermined timing, and a secondary transfer bias is applied to the backup roller 24. The applied transfer bias has a (-) polarity, the same as the polarity of the toner (-). Electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, transferring the toner image on the intermediate transfer belt 20 to the recording paper P. The secondary transfer bias is determined by the resistance detected by a resistance detection device (not shown) that detects the resistance of the secondary transfer section and is voltage-controlled.

[0411] Then, the recording paper P is fed into a pressure-contact portion (nip portion) of a pair of fixing rollers in a fixing device (an example of a fixing device) 28 , where the toner image is fixed on the recording paper P, thereby forming a fixed image.

[0412] Examples of the recording paper P to which the toner image is transferred include plain paper used in electrophotographic copy machines, printers, etc. Examples of the recording medium include OHP sheets and the like in addition to the recording paper P.

[0413] To further improve the smoothness of the image surface after fixing, the surface of the recording paper P is preferably smooth. For example, coated paper obtained by coating the surface of plain paper with a resin or coated paper for printing can be preferably used.

[0414] The recording paper P on which the color image has been fixed is conveyed toward the discharge portion, thereby completing a series of color image forming operations.

[0415] <Process Cartridge / Toner Cartridge>

[0416] The process cartridge according to this embodiment will be described.

[0417] The process cartridge according to this embodiment is provided with a developing device and is detachably mounted on an image forming apparatus. The developing device accommodates the electrostatic image developer according to this embodiment and develops the electrostatic image formed on the surface of the image holder into a toner image using the electrostatic image developer.

[0418] The process cartridge according to this embodiment is not limited to the above-described structure, and may include a developing device and, if necessary, at least one other device selected from an image holder, a charging device, an electrostatic image forming device, and a transfer device.

[0419] Hereinafter, an example of the process cartridge according to the present embodiment is shown, but the present invention is not limited thereto.

[0420] Figure 2 It is a diagram schematically showing the structure of a process cartridge according to this embodiment.

[0421] Figure 2 The processing box 200 shown is constructed by, for example, integrally combining and holding a photosensitive body 107 (an example of an image holding body), a charging roller 108 (an example of a charging device) provided around the photosensitive body 107, a developing device 111 (an example of a developing device), and a photosensitive body cleaning device 113 (an example of a cleaning device) using a housing 117 having a mounting guide 116 and an opening 118 for exposure, and is made into a box.

[0422] in addition, Figure 2 109 denotes an exposure device (an example of an electrostatic image forming device), 112 denotes a transfer device (an example of a transfer device), 115 denotes a fixing device (an example of a fixing device), and 300 denotes recording paper (an example of a recording medium).

[0423] Next, the toner cartridge according to this embodiment will be described.

[0424] The toner cartridge according to the present embodiment contains the toner according to the present embodiment and is attachable to and detachable from an image forming apparatus. The toner cartridge contains replenishing toner for supplying to a developing device provided in the image forming apparatus.

[0425] in addition, Figure 1 The image forming apparatus shown has a structure in which toner cartridges 8Y, 8M, 8C, and 8K are detachably mounted. The developing devices 4Y, 4M, 4C, and 4K are connected to the toner cartridges corresponding to the respective developing devices (colors) via toner supply tubes (not shown). When the toner contained in a toner cartridge becomes low, the toner cartridge is replaced.

[0426] Example

[0427] Hereinafter, examples will be described, but the present invention is not limited to these examples. In the following description, "parts" and "%" are all based on mass unless otherwise specified.

[0428] [Preparation of emulsions (1-1) to (1-2)]

[0429] <Emulsion (1-1)>

[0430] Styrene: 80 parts

[0431] n-Butyl acrylate: 120 parts

[0432] 1,10-Decanediol diacrylate (crosslinking agent): 4 parts

[0433] Anionic surfactant (ELEMINOL MON-2, manufactured by Sanyo Chemical Industries, Ltd.): 1.2 parts

[0434] Ion exchange water: 98.8 parts

[0435] The above materials were placed in a mixing container equipped with a stirring device and stirred to prepare an emulsion (1-1).

[0436] <Emulsion (1-2)>

[0437] Styrene: 75 parts

[0438] n-Butyl acrylate: 25 parts

[0439] 1,10-Decanediol diacrylate (crosslinking agent): 1.1 parts

[0440] Anionic surfactant (ELEMINOL MON-2): 1.2 parts

[0441] Ion exchange water: 98.8 parts

[0442] The above materials were placed in a mixing container equipped with a stirring device and stirred to prepare an emulsion (1-2).

[0443] [Preparation of internally added cross-linked resin particle dispersion (1)]

[0444] After nitrogen substitution in a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 0.5 parts of anionic surfactant (NEWCOL 271A) and 200 parts of ion-exchanged water were added to the reaction vessel. The reaction solution was heated in an oil bath while stirring to a temperature of 65°C. After adding 10 parts of emulsion (1-1), 20 parts of an aqueous ammonium persulfate solution adjusted to a concentration of 10% by mass was added as polymerization initiator 1, and the mixture was maintained for 30 minutes.

[0445] Then, while maintaining the temperature of the reaction solution at 65° C., 390 parts of the emulsion (1-1) were gradually added dropwise to the reaction container using a pump over 60 minutes. Furthermore, 200 parts of the emulsion (1-2) were added dropwise over 30 minutes.

[0446] After the addition was completed, the mixture was maintained for 60 minutes, and then 2 parts of 10% by mass ammonium persulfate were added as polymerization initiator 2. The mixture was maintained for another 3 hours, and then cooled to room temperature. Then, ion-exchanged water was added to obtain a solid content concentration of 20% by mass, thereby preparing an internally added crosslinked resin particle dispersion (1).

[0447] The volume average particle size of the obtained resin particles was 165 nm, and the glass transition temperature Tg measured by a differential scanning calorimeter was 17°C.

[0448] [Preparation of dispersions of internally added cross-linked resin particles (2) to (9)]

[0449] Internally added crosslinked resin particle dispersions (2) to (9) were prepared in the same manner as the internally added crosslinked resin particle dispersion (1) except that the conditions were changed to those shown in Table 1.

[0450] In addition, in Table 1, "St ratio" represents the mass ratio (mass %) of styrene.

[0451] [Preparation of Styrene Acrylic Resin Particle Dispersion C8]

[0452] Styrene: 47.9 parts

[0453] n-Butyl acrylate: 51.8 parts

[0454] 2-Carboxyethyl acrylate: 0.3 parts

[0455] Anionic surfactant (manufactured by The Dow Chemical Company, Dowfax 2A1): 0.8 parts

[0456] 1,10-Decanediol diacrylate: 1.65 parts

[0457] The above raw materials were mixed and dissolved, 60 parts of ion-exchanged water was added, and the mixture was dispersed and emulsified in a flask to prepare an emulsion.

[0458] Next, 1.3 parts of anionic surfactant (Dowfax 2A1 manufactured by The Dow Chemical Company) was dissolved in 90 parts of ion-exchanged water, 1 part of the emulsion was added thereto, and 10 parts of ion-exchanged water in which 5.4 parts of ammonium persulfate was dissolved was further added.

[0459] Then, the remaining portion of the emulsion was added over 180 minutes, and after nitrogen substitution in the flask, the solution in the flask was heated to 65° C. in an oil bath while stirring. Emulsion polymerization was continued in this state for 500 minutes to obtain a styrene acrylic resin particle dispersion C8 with a solid content adjusted to 24.5% by mass.

[0460] [Preparation of amorphous polyester resin particle dispersion (1)]

[0461] Dodecenylsuccinic anhydride: 12 mol parts

[0462] Terephthalic acid: 25 parts by mole

[0463] Fumaric acid: 10 mol parts

[0464] Trimellitic anhydride: 2 mol parts

[0465] Bisphenol A propylene oxide 2 mole adduct: 40 moles

[0466] Bisphenol A ethylene oxide 2 mole adduct: 10 moles

[0467] The above materials were placed in a reaction vessel equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor, and a distillation column. The temperature was raised to 190°C over 1 hour, and 1.2 parts of dibutyltin oxide was added to 100 parts of the above materials. While distilling off the generated water, the temperature was raised to 240°C over 6 hours. Subsequently, a dehydration condensation reaction was continued at 240°C for 3 hours, and then cooled to obtain an amorphous polyester resin (1).

[0468] Amorphous polyester resin (1): 100 parts

[0469] Methyl ethyl ketone: 60 parts

[0470] Isopropyl alcohol: 10 parts

[0471] 10% ammonia solution: 3.5 parts

[0472] The above materials were placed in a jacketed reaction vessel equipped with a condenser, a thermometer, a water dripping device, and an anchor wing. The amorphous polyester resin (1) was dissolved while being stirred and mixed at 100 rpm in a water-circulating thermostatic bath while maintaining the liquid temperature at 50°C. Subsequently, the water-circulating thermostatic bath was set to 40°C, and a total of 300 parts of ion-exchanged water maintained at 40°C was added dropwise at a rate of 3 parts / minute to effect phase inversion, thereby producing an emulsion.

[0473] The obtained emulsion was placed in an eggplant-shaped flask and placed in an evaporator equipped with a vacuum control unit via a trap ball. The eggplant-shaped flask was heated in a 60°C hot water bath while rotating, and the pressure was reduced to 7 kPa while paying attention to boiling. After removing the solvent, the pressure was returned to normal pressure and the eggplant-shaped flask was water-cooled to obtain a dispersion. Ion-exchanged water was added to the obtained dispersion to obtain an amorphous polyester resin particle dispersion (1) with a solid content of 20% by mass. The volume average particle size of the amorphous polyester resin particles in the amorphous polyester resin particle dispersion (1) was 180 nm.

[0474] [Preparation of Amorphous Polyester Resin Particle Dispersions (2) to (19)]

[0475] Amorphous polyester resin particle dispersions (2) to (19) were prepared in the same manner as in the amorphous polyester resin particle dispersion (1), except that the conditions were changed to those shown in Table 2.

[0476] In addition, the details of the abbreviations in Table 2 are as follows.

[0477] TPA: terephthalic acid

[0478] FA: Fumaric acid

[0479] IPA: Isophthalic acid

[0480] TMA: trimellitic anhydride

[0481] BPA-2PO: Bisphenol A propylene oxide 2 mole adduct

[0482] BPA-3PO: Bisphenol A propylene oxide 3 mole adduct

[0483] BPA-2EO: Bisphenol A ethylene oxide 2 mole adduct

[0484] PC: A monomer for forming a structural unit derived from a polycarboxylic acid having at least one of an alkyl group and the alkenyl group (ie, a polycarboxylic acid)

[0485] PA: A monomer for forming a structural unit derived from a polyol having at least one of an alkyl group and the alkenyl group (ie, a polyol)

[0486] <Preparation of Amorphous Polyester Resin Particle Dispersion (C8)>

[0487] Terephthalic acid: 28 parts

[0488] Fumaric acid: 164 parts

[0489] Adipic acid: 10 parts

[0490] Bisphenol A ethylene oxide 2 mole adduct: 26 parts

[0491] Bisphenol A propylene oxide 2 mole adduct: 542 parts

[0492] The above materials were placed in a reaction vessel equipped with a stirrer, nitrogen inlet pipe, temperature sensor, and distillation column. The temperature was raised to 190°C over 1 hour, and 1.2 parts of dibutyltin oxide (100 parts) of the above materials were added. While distilling off the generated water, the temperature was raised to 240°C over 6 hours and maintained at 240°C. After a dehydration condensation reaction was continued for 3 hours, the reaction mixture was cooled.

[0493] The reactants were transferred to a Cavitron CD1010 (manufactured by EUROTEC LIMITED) in a molten state at a rate of 100 g per minute. Simultaneously, a separately prepared ammonia solution with a concentration of 0.37% by mass was heated to 120° C. using a heat exchanger and transferred to the Cavitron CD1010 at a rate of 0.1 liter per minute. The rotor was rotated at 60 Hz and the pressure was 5 kg / cm 2 A Cavitron CD1010 was operated under conditions of 100 nm to obtain a resin particle dispersion containing amorphous polyester resin particles having a volume average particle size of 169 nm. Ion-exchanged water was added to the resin particle dispersion to adjust the solid content to 20% by mass, thereby producing an amorphous polyester resin particle dispersion (C8).

[0494] [Preparation of Crystalline Polyester Resin Particle Dispersion (1)]

[0495] Dodecanedioic acid: 50 mol parts

[0496] 1,6-Hexanediol: 50 parts by mole

[0497] The above materials were placed in a reaction vessel equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor, and a distillation tower. The temperature was raised to 160°C over 1 hour, and 0.8 parts of dibutyltin oxide were added relative to 100 parts of the above materials. While distilling off the generated water, the temperature was raised to 180°C over 6 hours, maintained at 180°C, stirred for 5 hours, and refluxed in the vessel to react. Then, the temperature was gradually raised to 230°C under reduced pressure (3 kPa), maintained at 230°C, and stirred for 2 hours. Then, the reactant was cooled. After cooling, solid-liquid separation was performed, and the solid matter was dried to obtain a crystalline polyester resin (1). The weight average molecular weight of the crystalline polyester resin (1) was 29,000.

[0498] Crystalline polyester resin (1): 100 parts

[0499] Methyl ethyl ketone: 70 parts

[0500] Isopropyl alcohol: 12 parts

[0501] 10% ammonia solution: 3 parts

[0502] The above materials were placed in a jacketed reaction vessel equipped with a condenser, a thermometer, a water dripping device, and an anchor wing. While maintaining the liquid temperature at 80°C in a water-circulating thermostatic bath, the crystalline polyester resin (1) was dissolved while being stirred and mixed at 100 rpm. Subsequently, the water-circulating thermostatic bath was set to 60°C, and a total of 300 parts of ion-exchanged water maintained at 60°C was added dropwise at a rate of 3 parts / minute to effect phase inversion, thereby obtaining an emulsion.

[0503] The obtained emulsion was placed in an eggplant-shaped flask and placed in an evaporator equipped with a vacuum control unit via a trap ball. The eggplant-shaped flask was heated in a 60°C hot water bath while rotating, and the pressure was reduced to 7 kPa while paying attention to boiling. After removing the solvent, the pressure was returned to normal pressure and the eggplant-shaped flask was water-cooled to obtain a dispersion. Ion-exchanged water was added to the dispersion to obtain a crystalline polyester resin particle dispersion (1) having a solid content of 20% by mass. The volume average particle size of the crystalline polyester resin particles in the crystalline polyester resin particle dispersion (1) was 160 nm.

[0504] (Preparation of Crystalline Polyester Resin Particle Dispersion (C8))

[0505] 1,10-Dodecanedioic acid: 225 parts

[0506] 1,6-Hexanediol: 143 parts

[0507] The above materials were placed in a reaction vessel equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor, and a distillation column. The temperature was raised to 160°C over 1 hour, and 0.8 parts by mass of dibutyltin oxide was added. While distilling off the generated water, the temperature was raised to 180°C over 6 hours and maintained at 180°C for 5 hours of dehydration condensation reaction. Then, the temperature was gradually raised to 230°C under reduced pressure and maintained at 230°C, with stirring for 2 hours. The reactants were then cooled. After cooling, solid-liquid separation was performed, and the solid matter was dried to obtain a crystalline polyester resin (C8).

[0508] Crystalline polyester resin (C8): 100 parts

[0509] Methyl ethyl ketone: 40 parts

[0510] Isopropyl alcohol: 30 parts

[0511] 10% ammonia solution: 6 parts

[0512] The above materials were added to a 3-liter jacketed reaction vessel (BJ-30N, manufactured by Tokyo Rikakikai Co., Ltd.) equipped with a condenser, thermometer, dripping device, and anchor fins. The mixture was stirred and mixed at 100 rpm while maintaining the temperature at 80°C in a water-circulating thermostatic bath to dissolve the resin. The thermostatic bath was then set to 50°C, and a total of 400 parts of ion-exchanged water maintained at 50°C was added dropwise at a rate of 7 parts by mass / minute to effect phase inversion, resulting in an emulsion. 576 parts by mass of the resulting emulsion and 500 parts by mass of ion-exchanged water were placed in a 2-liter eggplant-shaped flask, which was then placed in an evaporator equipped with a vacuum control unit (manufactured by Tokyo Rikakikai Co., Ltd.) via a trap ball. The flask was heated in a 60°C hot water bath while rotating. While ensuring a boiling point, the pressure was reduced to 7 kPa, and the solvent was removed. The volume average particle size (D50v) of the resin particles in this dispersion was 185 nm. Then, ion-exchanged water was added to obtain a crystalline polyester resin particle dispersion (C8) having a solid content concentration of 22.1% by mass.

[0513] [Preparation of Colorant Dispersion]

[0514] Carbon black (Regel 330, manufactured by Cabot Corporation): 110 parts

[0515] Anionic surfactant (NEOPELEX G-65, Kao Corporation): 6 parts

[0516] Ion exchange water: 300 parts

[0517] The above materials were mixed and dispersed for 10 minutes using a homogenizer (ULTRA TURRAX T50, manufactured by IKA). Ion-exchanged water was added to the resulting dispersion to obtain a colorant dispersion having a solids content of 20% by mass. The volume average particle size of the colorant particles in the colorant dispersion was 220 nm.

[0518] [Preparation of Release Agent Particle Dispersion]

[0519] Fischer-Tropsch wax (SASOLWAX H1, SASOL): 100 parts

[0520] Anionic surfactant (NEOPELEX G-65): 6 parts

[0521] Ion exchange water: 300 parts

[0522] The above materials were mixed, heated to 100°C, and dispersed using a homogenizer (ULTRA TURRAX T50). Furthermore, the mixture was dispersed using a Manton-Gaulin high-pressure homogenizer (manufactured by Gaulin). Ion-exchanged water was added to the dispersion to obtain a release agent particle dispersion having a solid content of 20% by mass.

[0523] The volume average particle size of the release agent particles in the release agent particle dispersion was 230 nm.

[0524] [Example 1]

[0525] (Preparation of Toner 1)

[0526] Amorphous polyester resin particle dispersion (1) (solid content 20% by mass): 59.12 parts

[0527] Internally added cross-linked resin particle dispersion (1) (solid content 20% by mass): 10 parts

[0528] Crystalline polyester resin particle dispersion (1) (solid content 20% by mass): 14.78 parts

[0529] Colorant dispersion (solid content 20% by mass): 10.6 parts

[0530] Release agent particle dispersion (solid content 20% by mass): 5.5 parts

[0531] Anionic surfactant (ELEMINOL MON-2): 1.6 parts

[0532] Ion exchange water: 80 parts

[0533] The above materials were placed in a reaction vessel (1) equipped with a thermometer, pH meter, and stirrer. The reaction vessel was maintained at 20°C while stirring at 150 rpm for 30 minutes. Subsequently, 0.3N nitric acid aqueous solution was added to adjust the pH to 4.5. A 2% aluminum sulfate aqueous solution was then added while dispersing the mixture using a homogenizer (ULTRA TURRAX T50). The temperature was then raised to 30°C at a rate of 0.4°C / min while stirring and maintained for 30 minutes.

[0534] Next, 29 parts of the amorphous polyester resin particle dispersion (1) was added and the mixture was maintained for 30 minutes. A 0.1N sodium hydroxide aqueous solution was then added to adjust the pH to 8.5, and the mixture was maintained for 15 minutes. The mixture was then heated to 80°C at a rate of 1°C / min while continuously stirring and maintained at 80°C for 5 hours. The mixture was then cooled, solid-liquid separated, and the solid matter was washed with ion-exchanged water. The mixture was then dried in a freeze vacuum dryer for 24 hours to obtain toner particles (1) having a volume average particle size of 5.5 μm.

[0535] Toner 1 was obtained by mixing 100 parts of the toner particles (1) and 2.0 parts of hydrophobic silica (manufactured by NIPPON AEROSIL CO., LTD.: trade name RY200) using a Henschel mixer.

[0536] [Examples 2 to 44 and Comparative Examples 1 to 7]

[0537] (Production of Toners 2 to 44 and Toners C1 to C7)

[0538] Toner 1 was prepared in the same manner as described in Tables 3-1 to 3-6, except that the types and amounts of the resin particle dispersions were changed. The solid content of each resin particle dispersion was set to 20% by mass.

[0539] In addition, the amorphous polyester resin particle dispersion liquid added later was also changed as shown in Tables 3-1 to 3-6.

[0540] Furthermore, in Example 36, two types of amorphous polyester resin particle dispersions added later were used simultaneously at a mass ratio of 1:1.

[0541] Furthermore, in Examples 37 to 39, the quantitative ratio of the amorphous polyester resin particle dispersions 17 and 12 is adjusted so that the molar ratio of the "structural units derived from polycarboxylic acids having alkyl or alkenyl groups" (i.e., the proportion of the structural units derived from polycarboxylic acids having at least one of alkyl and alkenyl groups relative to all structural units constituting the amorphous polyester resin) becomes the value shown in the table.

[0542] In Examples 37 to 39, the amorphous polyester resin particle dispersions 17 and 12 were used in combination at the charge amount ratio.

[0543] [Comparative Example 8]

[0544] (Production of Toner C8)

[0545] Amorphous polyester resin particle dispersion (C8): 169 parts

[0546] Styrene acrylic resin particle dispersion (C8): 33 parts

[0547] Crystalline polyester resin particle dispersion (C8): 53 parts

[0548] Release agent particle dispersion (2): 25 parts

[0549] Colorant dispersion (1): 33 parts

[0550] Anionic surfactant (manufactured by The Dow Chemical Company, Dowfax 2A1): 4.8 parts

[0551] The raw materials, whose liquid temperature was adjusted to 10° C., were placed in a 3 L cylindrical stainless steel container and dispersed and mixed for 2 minutes using a homogenizer (ULTRA TURRAX T50 manufactured by IKA) at 4000 rpm while applying a shear force.

[0552] Next, 1.75 parts of a 10% nitric acid aqueous solution of aluminum sulfate as a coagulant was gradually added dropwise, and the homogenizer was rotated at 10,000 rpm to perform dispersion mixing for 10 minutes to prepare a raw material dispersion.

[0553] The raw material dispersion was then transferred to a polymerization reactor equipped with a two-paddle stirring device and a thermometer. The stirring speed was set to 550 rpm, and heating was initiated in a heating pack to promote the growth of aggregated particles at 40°C. Furthermore, the pH of the raw material dispersion was controlled within the range of 2.2 to 3.5 using 0.3 M nitric acid and 1 M sodium hydroxide aqueous solutions. The pH was maintained within this range for approximately 2 hours, resulting in the formation of aggregated particles.

[0554] Next, a dispersion obtained by mixing 21 parts of amorphous polyester resin particle dispersion (C8) and 8 parts of styrene acrylic resin particle dispersion (C8) was added and held for 60 minutes to allow the binder resin particles and styrene acrylic resin particles (C8) to adhere to the surfaces of the aggregated particles. Furthermore, the temperature was raised to 53°C, and then 21 parts of amorphous polyester resin particle dispersion (C8) was added and held for 60 minutes to allow the binder resin particles to adhere to the surfaces of the aggregated particles.

[0555] The aggregated particles were aligned while confirming the particle size and morphology using an optical microscope and a particle / cell counter and particle size analyzer (Multisizer 3). The pH was then adjusted to 7.8 using a 5% aqueous sodium hydroxide solution and maintained for 15 minutes.

[0556] To fuse the aggregated particles, the pH was raised to 8.0 and the temperature was raised to 85°C. After confirming the fusion of the aggregated particles using an optical microscope, heating was stopped after 2 hours and the mixture was cooled at a rate of 1.0°C / min. The mixture was then sieved with a 20 μm mesh, repeatedly washed with water, and dried in a vacuum dryer to obtain toner particles (C8) having a volume average particle size of 5.3 μm.

[0557] 100 parts of the toner particles (C8) and 2.0 parts of hydrophobic silica (manufactured by NIPPON AEROSIL CO., LTD.: trade name RY200) are mixed with a Henschel mixer to obtain Toner C8.

[0558] The following parameters are shown for the toners obtained in Examples 1 to 44 and Comparative Examples 1 to 8. The methods for measuring the characteristics of the toners are as described above.

[0559] The ratio (molar %) of the structural unit derived from a polycarboxylic acid having at least one of an alkyl group and an alkenyl group (indicated as "structural unit derived from a polycarboxylic acid having an alkyl group or an alkenyl group" in the table) to all structural units constituting the amorphous polyester resin

[0560] The ratio (molar %) of the structural unit derived from a polyol having at least one of an alkyl group and an alkenyl group (indicated as "structural unit derived from a polyol having an alkyl group or an alkenyl group" in the table) to all structural units constituting the amorphous polyester resin

[0561] · Content of crystalline polyester resin relative to binder resin

[0562] Content Wa of amorphous polyester resin relative to toner particles

[0563] Content of internally added cross-linked resin particles relative to toner particles Wb

[0564] · Content Wc of crystalline polyester resin relative to toner particles

[0565] Storage elastic modulus G' of the internally added cross-linked resin particles (styrene-(meth)acrylic acid copolymer particles: StAc particles) within the range of 60°C to 100°C (specifically, storage elastic modulus G' at 60°C and 100°C). In the table, "10^5" means "10 5 ","10^6" means "10 6 ”.

[0566] Average dispersion diameter of added cross-linked resin particles

[0567] Dielectric loss coefficient at 1 kHz in the toner after being left at a temperature of 28°C and a relative humidity of 85% RH

[0568] [evaluate]

[0569] (Production of Developer)

[0570] 8 parts of each toner obtained in each example and 92 parts of the following carrier were mixed to obtain a developer. The obtained developer was used in the evaluation described below.

[0571] (Carrier Preparation)

[0572] Ferrite particles (average particle size 35 μm): 100 parts

[0573] Toluene: 14 parts

[0574] Styrene / methyl methacrylate copolymer (copolymer ratio 15 / 85): 3 parts

[0575] Carbon black: 0.2 parts

[0576] The above components except the ferrite particles were dispersed in a sand mill to prepare a dispersion, and the dispersion was placed in a vacuum degassing kneader together with the ferrite particles, and dried under reduced pressure while stirring to obtain a carrier.

[0577] (Low-temperature fixability)

[0578] The developer obtained was filled into the developing unit of a color copier Apeos C6570 (manufactured by FUJIFILM Business Innovation Corp.) with the fixing unit removed, and the toner load was adjusted to 9.0 g / cm 2Colotech 90 paper (manufactured by Xerox Corporation / basis weight 90 gsm) was used as the recording medium. The output image had a size of 50 mm x 50 mm and an image density of 100%.

[0579] The unfixed images were then fixed using a fixing evaluation device, and low-temperature fixing properties were evaluated. A fixing device was used, which had been modified from the fixing unit of a FUJIFILM Business Innovation Corp. Apeos C6570, manufactured by FUJIFILM Business Innovation Corp., to allow for variable fixing temperatures. The fixing temperature was increased in 5°C increments from 120°C to 190°C. The temperature at which image defects caused by offset (a phenomenon in which toner does not sufficiently melt and adheres to the fixing component) ceased to occur was defined as the minimum fixing temperature, and the images were classified as follows.

[0580] A: The minimum fixing temperature is below 145°C

[0581] B: The minimum fixing temperature is more than 145°C and less than 155°C

[0582] C: The minimum fixing temperature is higher than 155°C and lower than 165°C

[0583] D: Minimum fixing temperature is above 165℃

[0584] (Uneven transfer)

[0585] Each of the prepared developers was filled in a developing device of a color copier Apeos C6570 (manufactured by FUJIFILM Business Innovation Corp.), which is an apparatus for image evaluation.

[0586] An image was formed using an image evaluation device with the fixing temperature set to the above-mentioned minimum fixing temperature + 15°C. Specifically, 50,000 images with an image density of 1% were printed continuously on C2 A4 paper at a temperature of 28°C and a relative humidity of 85%. The paper was then placed in a tray and left in the same environment for 24 hours. First thing in the morning, 10 full-surface halftone images with an image density of 80% were printed on C2 A4 paper. The density of the 10th printed image was then randomly measured at 10 points using an image densitometer, X-Rite 938 (manufactured by X-Rite). The difference between the maximum and minimum values, i.e., the image density difference, was determined, and image density unevenness was evaluated according to the following criteria. In the evaluation, C was set as the allowable range.

[0587] A+: Image density difference is 1% or less

[0588] A: Image density difference is 5% or less

[0589] B: Image density difference is more than 5% and less than 8%

[0590] C: Image density difference is more than 8% and less than 10%

[0591] D: Image density difference exceeds 10%

[0592]

[0593]

[0594]

[0595]

[0596]

[0597]

[0598]

[0599]

[0600] From the above results, it is understood that the toner of this example has low-temperature fixing properties and can suppress transfer unevenness compared to the toner of the comparative example.

[0601] This embodiment includes the following aspects. (1)

[0603] A toner for developing electrostatic images, comprising toner particles containing an amorphous polyester resin and a crystalline polyester resin as binder resins and internally added crosslinked resin particles.

[0604] The toner particles contain an amorphous polyester resin (S) as the amorphous polyester resin, wherein the amorphous polyester resin (S) has at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms.

[0605] The content of the crystalline polyester resin is 10% by mass or more and 40% by mass or less relative to the binder resin,

[0606] The storage modulus G' of the internally added cross-linked resin particles in the range of 60°C to 100°C is 1.0×10 5 Pa or more and 1.0×10 6 Pa or less styrene-(meth)acrylic acid copolymer particles. (2)

[0608] The electrostatic image developing toner according to (1), wherein

[0609] A ratio Wb / Wa of a content Wa of the amorphous polyester resin to a content Wb of the internally added crosslinked resin particles relative to the toner particles is 0.05 or more and 0.50 or less in terms of mass ratio. (3)

[0611] The electrostatic image developing toner according to (2), wherein

[0612] A ratio Wb / Wa of a content Wa of the amorphous polyester resin to a content Wb of the internally added crosslinked resin particles relative to the toner particles is 0.10 or more and 0.35 or less in terms of mass ratio. (4)

[0614] The electrostatic image developing toner according to any one of (1) to (3), wherein

[0615] A ratio Wb / Wc of a content Wc of the crystalline polyester resin to a content Wb of the internally added crosslinked resin particles relative to the toner particles is 0.20 or more and 2.00 or less in terms of mass ratio. (5)

[0617] The electrostatic image developing toner according to (4), wherein

[0618] A ratio Wb / Wc of a content Wc of the crystalline polyester resin to a content Wb of the internally added crosslinked resin particles relative to the toner particles is 0.50 or more and 1.00 or less in terms of mass ratio. (6)

[0620] The electrostatic image developing toner according to any one of (1) to (5), wherein

[0621] The amorphous polyester resin (S) is an amorphous polyester resin having a structural unit PC derived from a polycarboxylic acid and a structural unit PA derived from a polyol.

[0622] At least a portion of the structural units PC and PA are structural units having at least one of the alkyl group and the alkenyl group.

[0623] The ratio of the structural unit having at least one of the alkyl group and the alkenyl group is 2 mol% or more and 25 mol% or less in terms of a molar ratio relative to all structural units constituting the amorphous polyester resin. (7)

[0625] The electrostatic image developing toner according to (6), wherein

[0626] The ratio of the structural unit having at least one of the alkyl group and the alkenyl group is 5 mol% or more and 20 mol% or less in terms of a molar ratio relative to all structural units constituting the amorphous polyester resin. (8)

[0628] The electrostatic image developing toner according to (6) or (7), wherein

[0629] At least one of the alkyl group and the alkenyl group is present only in at least a portion of the structural units PC derived from the polycarboxylic acid. (9)

[0631] The electrostatic image developing toner according to any one of (1) to (8), wherein

[0632] The average dispersion diameter of the internally added cross-linked resin particles is 100 nm or more and 300 nm or less. (10)

[0634] The electrostatic image developing toner according to any one of (1) to (9), wherein

[0635] The dielectric loss coefficient of the toner at 1 kHz after being left at a temperature of 28° C. and a relative humidity of 85% RH is 35×10 -3 the following. (11)

[0637] The electrostatic image developing toner according to any one of (1) to (10), wherein

[0638] The toner particles contain carbon black as a colorant. (12)

[0640] An electrostatic image developer comprising the electrostatic image developing toner according to any one of (1) to (11). (13)

[0642] A toner cartridge containing the electrostatic image developing toner described in any one of (1) to (11),

[0643] The image forming apparatus is mounted and removed from the image forming apparatus. (14)

[0645] A process cartridge comprising a developing device that accommodates the electrostatic image developer described in (12) and develops an electrostatic image formed on a surface of an image holding member into a toner image using the electrostatic image developer.

[0646] The process cartridge is attachable to and detachable from the image forming apparatus. (15)

[0648] An image forming apparatus comprising:

[0649] Image holding body;

[0650] a charging device for charging the surface of the image holding member;

[0651] an electrostatic image forming device for forming an electrostatic image on the charged surface of the image holding member;

[0652] a developing device that accommodates the electrostatic image developer described in (12) and develops the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer;

[0653] a transfer device that transfers the toner image formed on the surface of the image holding member to the surface of a recording medium; and

[0654] The fixing device fixes the toner image transferred onto the surface of the recording medium. (16)

[0656] An image forming method comprising:

[0657] a charging process for charging the surface of the image holding member;

[0658] an electrostatic image forming step of forming an electrostatic image on the charged surface of the image holding member;

[0659] a developing step of developing the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer described in (12);

[0660] a transfer step of transferring the toner image formed on the surface of the image holding member to the surface of a recording medium; and

[0661] The fixing step fixes the toner image transferred onto the surface of the recording medium.

[0662] The effects of the above method are as follows.

[0663] According to the invention according to (1), there is provided a toner for electrostatic image development having toner particles comprising an amorphous polyester resin and a crystalline polyester resin as a binder resin and internally added crosslinked resin particles, wherein the content of the crystalline polyester resin relative to the binder resin is 10% by mass or more and 40% by mass or less, the amorphous polyester resin is exclusively an amorphous polyester resin having no at least one of an alkyl group having 8 or more and 15 or less carbon atoms and an alkenyl group having 8 or more and 15 or less carbon atoms, and the internally added crosslinked resin particles have a storage elastic modulus G' of less than 1.0×10 5 Pa or more than 1.0×10 6 In the case of the styrene-(meth)acrylic acid-based copolymer particles of Pa, low-temperature fixing properties are achieved, and transfer unevenness can be suppressed.

[0664] According to the invention described in (2), there is provided a toner for electrostatic image development having low-temperature fixing properties and capable of suppressing transfer unevenness, compared to a case where the ratio Wb / Wa of the content Wa of the amorphous polyester resin to the content Wb of the internally added cross-linked resin particles relative to the toner particles is less than 0.05 or exceeds 0.50 in terms of mass ratio.

[0665] According to the invention described in (3), there is provided a toner for electrostatic image development having low-temperature fixing properties and capable of suppressing transfer unevenness, compared to a case where the ratio Wb / Wa of the content Wa of the amorphous polyester resin to the content Wb of the internally added cross-linked resin particles relative to the toner particles is less than 0.10 or exceeds 0.35 in terms of mass ratio.

[0666] According to the invention described in (4), there is provided a toner for electrostatic image development having low-temperature fixing properties and capable of suppressing transfer unevenness, compared to a case where the ratio Wb / Wc of the content Wc of the crystalline polyester resin to the content Wb of the internally added cross-linked resin particles relative to the toner particles is less than 0.20 or exceeds 2.00 in terms of mass ratio.

[0667] According to the invention described in (5), there is provided a toner for electrostatic image development having low-temperature fixing properties and capable of suppressing transfer unevenness, compared to a case where the ratio Wb / Wc of the content Wc of the crystalline polyester resin to the content Wb of the internally added cross-linked resin particles relative to the toner particles is less than 0.50 or exceeds 1.00 in terms of mass ratio.

[0668] According to the invention according to (6), there is provided a toner for electrostatic image development which has low-temperature fixing properties and can suppress transfer unevenness, compared to a case where the proportion of structural units having at least one of an alkyl group and an alkenyl group is less than 2 mol % or exceeds 25 mol % in terms of the molar ratio relative to all structural units constituting the amorphous polyester resin.

[0669] According to the invention according to (7), there is provided a toner for electrostatic image development which has low-temperature fixing properties and can suppress transfer unevenness, compared to a case where the proportion of structural units having at least one of an alkyl group and an alkenyl group is less than 5 mol% or exceeds 20 mol% in terms of the molar ratio relative to all structural units constituting an amorphous polyester resin.

[0670] According to the invention according to (8), there is provided a toner for electrostatic image development that is low-cost, has low-temperature fixing properties, and can suppress transfer unevenness, compared to a case where at least one of an alkyl group and an alkenyl group is contained in at least a portion of the structural unit PA derived from a polyol.

[0671] According to the invention of (9), there is provided a toner for developing electrostatic images that has low-temperature fixing properties and can suppress transfer unevenness compared to a case where the average dispersion diameter of internally added cross-linked resin particles is less than 100 nm or exceeds 300 nm.

[0672] According to the invention of (10), there is provided a toner for electrostatic image development having a dielectric loss coefficient of more than 35×10 -3 In the case of , it has low-temperature fixing properties and can suppress transfer unevenness.

[0673] According to the invention according to (11), there is provided a toner for electrostatic image development as follows: compared with a case where, in a toner having toner particles comprising an amorphous polyester resin and a crystalline polyester resin as a binder resin and internally added crosslinked resin particles, the content of the crystalline polyester resin relative to the toner particles is 10% by mass or more and 40% by mass or less, the amorphous polyester resin is an amorphous polyester resin having no at least one of an alkyl group having 8 or more and 15 or less carbon atoms and an alkenyl group having 8 or more and 15 or less carbon atoms, and the internally added crosslinked resin particles have a storage modulus G' of less than 1.0×10 5 Pa or more than 1.0×10 6 In the case of the styrene-(meth)acrylic acid copolymer particles of Pa, even if the toner particles contain carbon black as a colorant, low-temperature fixing properties are achieved and transfer unevenness can be suppressed.

[0674] According to the invention of (12), (13), (14), (15) or (16), there is provided an electrostatic image developer, a toner cartridge, a process cartridge, an image forming apparatus or an image forming method as follows: compared to a case where, in a toner for electrostatic image development comprising toner particles containing an amorphous polyester resin and a crystalline polyester resin as a binder resin and internally added crosslinked resin particles, the content of the crystalline polyester resin relative to the toner particles is 10% by mass or more and 40% by mass or less, the amorphous polyester resin is an amorphous polyester resin having no at least one of an alkyl group having 8 or more and 15 or less carbon atoms and an alkenyl group having 8 or more and 15 or less carbon atoms, and the internally added crosslinked resin particles have a storage modulus G' of less than 1.0×10 5 Pa or more than 1.0×10 6 In the case of the styrene-(meth)acrylic acid-based copolymer particles of Pa, low-temperature fixing properties are achieved, and transfer unevenness can be suppressed.

[0675] The above-described embodiments of the present invention are provided for the purpose of illustration and explanation. In addition, the embodiments of the present invention do not fully and exhaustively include the present invention, and do not limit the present invention to the disclosed embodiments. It is obvious that various modifications and variations are self-evident to those skilled in the art to which the present invention belongs. The present embodiment is selected and described in order to most easily explain the principles of the present invention and its application. Thus, other technical personnel in this field can understand the present invention through various modifications optimized for specific uses of the assumed various embodiments. The scope of the present invention is defined by the above claims and their equivalents.

Claims

1. A toner for developing electrostatic images, comprising toner particles containing an amorphous polyester resin and a crystalline polyester resin as binder resins and internally added crosslinked resin particles, The toner particles contain an amorphous polyester resin (S) as the amorphous polyester resin, wherein the amorphous polyester resin (S) has at least one of an alkyl group having 8 to 15 carbon atoms and an alkenyl group having 8 to 15 carbon atoms. The content of the crystalline polyester resin is 10% by mass or more and 40% by mass or less relative to the binder resin, The storage modulus G' of the internally added cross-linked resin particles in the range of 60°C to 100°C is 1.0×10 5 Pa or more and 1.0×10 6 Pa or less styrene-(meth)acrylic acid copolymer particles.

2. The electrostatic image developing toner according to claim 1, wherein A ratio Wb / Wa of a content Wa of the amorphous polyester resin to a content Wb of the internally added crosslinked resin particles relative to the toner particles is 0.05 or more and 0.50 or less in terms of mass ratio.

3. The electrostatic image developing toner according to claim 2, wherein A ratio Wb / Wa of a content Wa of the amorphous polyester resin to a content Wb of the internally added crosslinked resin particles relative to the toner particles is 0.10 or more and 0.35 or less in terms of mass ratio. 4 . The electrostatic image developing toner according to claim 1 , wherein A ratio Wb / Wc of a content Wc of the crystalline polyester resin to a content Wb of the internally added crosslinked resin particles relative to the toner particles is 0.20 or more and 2.00 or less in terms of mass ratio.

5. The electrostatic image developing toner according to claim 4, wherein A ratio Wb / Wc of a content Wc of the crystalline polyester resin to a content Wb of the internally added crosslinked resin particles relative to the toner particles is 0.50 or more and 1.00 or less in terms of mass ratio. 6 . The electrostatic image developing toner according to claim 1 , wherein: The amorphous polyester resin (S) is an amorphous polyester resin having a structural unit PC derived from a polycarboxylic acid and a structural unit PA derived from a polyol. At least a portion of the structural units PC and PA are structural units having at least one of the alkyl group and the alkenyl group. The ratio of the structural unit having at least one of the alkyl group and the alkenyl group is 2 mol% or more and 25 mol% or less in terms of a molar ratio relative to all structural units constituting the amorphous polyester resin.

7. The electrostatic image developing toner according to claim 6, wherein The ratio of the structural unit having at least one of the alkyl group and the alkenyl group is 5 mol% or more and 20 mol% or less in terms of a molar ratio relative to all structural units constituting the amorphous polyester resin.

8. The electrostatic image developing toner according to claim 6 or 7, wherein At least one of the alkyl group and the alkenyl group is present only in at least a portion of the structural units PC derived from the polycarboxylic acid. 9 . The electrostatic image developing toner according to claim 1 , wherein The average dispersion diameter of the internally added cross-linked resin particles is 100 nm or more and 300 nm or less. 10 . The electrostatic image developing toner according to claim 1 , wherein The dielectric loss coefficient of the toner at 1 kHz after being left at a temperature of 28° C. and a relative humidity of 85% RH is 35×10 -3 the following. 11 . The electrostatic image developing toner according to claim 1 , wherein The toner particles contain carbon black as a colorant. 12 . An electrostatic image developer comprising the electrostatic image developing toner according to claim 1 .

13. A toner cartridge containing the electrostatic image developing toner according to any one of claims 1 to 11, The image forming apparatus is mounted and removed from the image forming apparatus.

14. A process cartridge comprising a developing device, the developing device housing the electrostatic image developer according to claim 12 and developing an electrostatic image formed on a surface of an image holding member into a toner image using the electrostatic image developer, The process cartridge is attachable to and detachable from the image forming apparatus.

15. An image forming apparatus comprising: Image holding body; a charging device for charging the surface of the image holding member; an electrostatic image forming device for forming an electrostatic image on the charged surface of the image holding member; a developing device that accommodates the electrostatic image developer according to claim 12 and develops the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer; a transfer device for transferring the toner image formed on the surface of the image holding member to the surface of a recording medium; and The fixing device fixes the toner image transferred onto the surface of the recording medium.

16. An image forming method comprising: a charging process for charging the surface of the image holding member; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image holding member; a developing step of developing the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer according to claim 12; a transfer step of transferring the toner image formed on the surface of the image holding member to the surface of a recording medium; and The fixing step fixes the toner image transferred onto the surface of the recording medium.

Citation Information

Patent Citations

  • Toner for electrophotography

    JP2010072215A

  • Toner for electrostatic charge image development

    JP2011257744A

  • Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method

    JP2016062042A

  • Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method

    JP2023048127A